Cr-Zr-N alloy material, alloy coating, alloy film product, application in high-brightness surface coating and preparation method
The Cr-Zr-N alloy material addresses the corrosion resistance issue of high-brightness alloy coatings by forming a densely structured coating with high brightness and corrosion resistance, improving durability and reducing material and production costs.
Patent Information
- Application Number
- CN202310749467.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2024-12-24
AI Technical Summary
Existing alloy coatings with high Cr content for enhancing surface brightness suffer from weak corrosion resistance, leading to corrosion issues during use.
A Cr-Zr-N alloy material with a specific atomic ratio (Cr x Zr y N z )M a, where x, y, z, and a are atomic ratios, forming a Cr-Zr-N alloy coating with a highly disordered and densely packed structure, providing both high brightness and corrosion resistance.
The Cr-Zr-N alloy coating achieves a brightness value of ≥70 with excellent corrosion resistance, outperforming traditional coatings in salt spray tests and reducing material usage, production costs, and environmental impact.
Smart Images

Figure CN119177444A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloy coatings, and in particular to Cr-Zr-N alloy materials and alloy coatings, alloy film products, and applications and preparation methods thereof in high-brightness surface coatings. Background Art
[0002] With the development of science and technology and the improvement of the quality of life, people are not only concerned about the practical performance of products in various fields such as automobiles, wearable products, 3C products, sports products, etc., but also gradually put forward higher requirements for the appearance of products. For example, the attention to the high brightness of the product surface has greatly increased. Among them, the representative "3C products" among these products are collectively referred to as computer, communication and consumer electronic products, also known as "information appliances", such as computers, tablets, mobile phones or digital audio players. Since 3C products are generally not large in size, they are often collectively referred to as "3C small appliances".
[0003] One of the methods to improve the surface brightness of traditional products is to use an alloy coating with a high Cr content. However, this type of coating usually has weak corrosion resistance and is prone to corrosion during use.
[0004] Therefore, it is necessary to develop new alloy coating materials in order to prepare alloy coatings with high brightness and good corrosion resistance. Summary of the invention
[0005] Based on this, the purpose of the present invention includes providing a Cr-Zr-N alloy material, which can form a Cr-Zr-N alloy coating with both high brightness and high corrosion resistance. When the Cr-Zr-N alloy coating is located on the surface of an alloy film product, it can simultaneously give the alloy film product high brightness and high corrosion resistance; in addition, the application of the aforementioned Cr-Zr-N alloy material or Cr-Zr-N alloy coating in high-brightness surface coating and the preparation method of the aforementioned Cr-Zr-N alloy coating are also provided.
[0006] In a first aspect of the present invention, a Cr-Zr-N alloy material is provided, wherein the chemical formula of the Cr-Zr-N alloy material is (Cr x Zr y N z )M a , M is a doping element, wherein x, y, z and a are each independently an atomic ratio, 47.1≤x≤81.6, 12.1≤y≤33.2, 4.7≤z≤35.9, and 0≤a / (x+y+z+a)≤0.05.
[0007] In some embodiments, the sum of x, y, and z is 100.
[0008] In some embodiments, y is greater than z.
[0009] In some embodiments, 63.19-0.925y≤x≤95.79-y and 31.4+0.9y≤x≤18.5y-171.85.
[0010] In some embodiments, the doping element is a non-metallic element, a metallic element, or a combination thereof;
[0011] The non-metallic elements include one or more of O, C, B, Si and Ar;
[0012] The metal elements include one or more of Ti, V, Nb, Mo, Hf, Ta, W, Ni, Mo, Fe, Ag, Au, Cu and Al.
[0013] In some embodiments, 0≤a / (x+y+z+a)≤0.02.
[0014] In a second aspect of the present invention, a Cr—Zr—N alloy coating is provided, wherein the Cr—Zr—N alloy coating comprises a film layer formed by the Cr—Zr—N alloy material according to the first aspect of the present invention.
[0015] In some embodiments, the Cr-Zr-N alloy coating satisfies the following two characteristics:
[0016] The X-ray diffraction pattern of the Cr-Zr-N alloy material or the Cr-Zr-N alloy coating has a peak in the diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of at least one 2θ (°) diffraction peak in the range of 30° to 50° satisfies ≥ 2°;
[0017] In the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy material or the Cr-Zr-N alloy coating, the characteristic atomic spacing is taken as the abscissa and the diffraction intensity is taken as the ordinate. There are diffraction peaks in the range of The half-width of at least one diffraction peak in the range satisfies
[0018] In some embodiments, the Cr—Zr—N alloy coating satisfies one or more of the following features:
[0019] The X-ray diffraction pattern of the Cr-Zr-N alloy coating is obtained by Cu target Kα ray;
[0020] The selected area electron diffraction pattern of the Cr-Zr-N alloy coating is obtained by using TEM characterization technology, with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm.
[0021] In some embodiments, the thickness of the Cr-Zr-N alloy coating is d min ~6μm, where d min Selected from 10nm to 50nm;
[0022] Optionally, d min 10 nm, 20 nm, 25 nm, 30 nm, 40 nm or 50 nm;
[0023] Optionally, the Cr—Zr—N alloy coating has a thickness of 1 μm to 2.5 μm.
[0024] In a third aspect of the present invention, an alloy film product is provided, comprising a substrate and the Cr—Zr—N alloy coating according to the second aspect of the present invention; wherein the Cr—Zr—N alloy coating is located on at least one side of the substrate.
[0025] In some embodiments, the surface material of the substrate is one of an alloy, a single metal and an inorganic non-metallic material;
[0026] The material type of the alloy includes one or more of nickel-based, iron-based, tungsten-based, titanium-based, silicon-based, aluminum-based, copper-based, cobalt-based, zirconium-based and zinc-based;
[0027] The elemental metal is any one of zinc, gold, platinum, zirconium, hafnium, niobium, tantalum, nickel, copper, aluminum, iron, silver and chromium;
[0028] The inorganic non-metallic material includes one or more of ceramics and glass.
[0029] In some embodiments, the surface material of the substrate is one of light alloys or one of stainless steel alloys; wherein the light alloy includes one or more of titanium alloy, aluminum alloy and magnesium alloy.
[0030] In some embodiments, the alloy film product satisfies one or more of the following characteristics:
[0031] The Cr-Zr-N alloy coating is in direct contact with the substrate or is provided with a transition layer;
[0032] The Cr-Zr-N alloy coating is located on the surface of the alloy film product or a surface layer is provided on the side of the Cr-Zr-N alloy coating away from the substrate, and the surface layer is a single-layer structure or a multi-layer structure.
[0033] In some embodiments, the alloy film product is one of 3C digital products, automotive products, aerospace products, wearable products and sports products.
[0034] In the fourth aspect of the present invention, there is provided an application of the Cr-Zr-N alloy material described in the first aspect of the present invention in the preparation of a high-brightness surface coating or an application of the Cr-Zr-N alloy coating described in the second aspect of the present invention as a high-brightness surface coating, wherein, tested by the Lab method, the brightness value L of the high-brightness surface coating is ≥70; wherein, the high-brightness surface coating is also a corrosion-resistant protective coating.
[0035] In the fifth aspect of the present invention, a method for preparing an alloy coating is provided, which comprises the following steps: using vapor deposition technology to deposit the constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of a substrate according to a preset atomic ratio, thereby forming the Cr-Zr-N alloy coating described in the second aspect of the present invention.
[0036] In some embodiments, the method for preparing the Cr-Zr-N alloy coating comprises the following steps: under the condition of introducing a mixed gas comprising argon and a nitrogen-containing gas, using one or more targets comprising chromium and zirconium, sputtering and depositing the constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of the substrate to form the Cr-Zr-N alloy coating.
[0037] In some embodiments, the preparation method meets one or more of the following characteristics:
[0038] The temperature of sputtering deposition is 30℃~330℃;
[0039] The total gas pressure of the mixed gas containing argon gas and nitrogen-containing gas is 0.3Pa to 1.2Pa;
[0040] The target material includes a chromium target and a zirconium target. The power density of the chromium target is 3.5 W / cm 2 ~6.7W / cm 2 , and the power density of the zirconium target is 0.5W / cm 2 ~3.0W / cm 2 ;
[0041] The target material includes an alloy target, and the alloy target includes at least two metal elements in the Cr-Zr-N alloy coating; optionally, the target material includes a chromium-zirconium-based alloy target, and the power density of the chromium-zirconium-based alloy target is 4W / cm 2 ~6W / cm 2 ;
[0042] The bias voltage of the substrate is -150V to -20V;
[0043] The sputtering deposition time is 10min to 150min;
[0044] The nitrogen-containing gas is nitrogen gas, and the gas flow rate of the nitrogen gas is 5 sccm to 52 sccm;
[0045] The nitrogen-containing gas is nitrogen, and the gas volume ratio of argon gas to nitrogen gas in the mixed gas is (2-6):1;
[0046] The Cr-Zr-N alloy material provided by the present invention mainly comprises three elements: Cr, Zr and N, and these three elements have a specific relative atomic ratio (Cr x Zr y N z ), 47.1≤x≤81.6, 12.1≤y≤33.2 and 4.7≤z≤35.9, so that the Cr-Zr-N alloy material has the ability to form highly disordered distribution and fully dense arrangement of atoms, and can form a Cr-Zr-N alloy coating with a dense structure. When the Cr-Zr-N alloy coating of the present invention is located on the surface of the product, it can not only give the product a high-brightness and beautiful surface, but also provide excellent corrosion resistance. The protection time of the Cr-Zr-N alloy coating containing the Cr-Zr-N alloy material of the present invention in the salt spray corrosion resistance test is much longer than that of the traditional Cr-Zr-N alloy coating.
[0047] In addition, the Cr-Zr-N alloy coating provided by the present invention can provide excellent corrosion resistance while also having high hardness characteristics, thereby better reducing scratches or weakening scratch damage. Further, the Cr-Zr-N alloy coating provided by the present invention can have both high corrosion resistance and high hardness characteristics at a relatively low thickness, which can save raw materials, simplify the process, shorten the production cycle, and significantly reduce costs.
[0048] The Cr-Zr-N alloy coating provided by the present invention can be used as the surface layer of the alloy film product, which has both beautiful decoration and the aforementioned protective effect. The Cr-Zr-N alloy coating provided by the present invention can also be located between the surface layers of the substrate and other structures, playing an excellent protective role, and can better resist corrosion and scratches.
[0049] The Cr-Zr-N alloy coating provided by the present invention can be applied to a variety of substrates, and the materials of the substrates include but are not limited to alloys, elemental metals, inorganic non-metallic materials and other substrates.
[0050] When the Cr-Zr-N alloy coating provided by the present invention appears in the protective coating of the alloy film product, the position of the Cr-Zr-N alloy coating can be flexibly set. For example, the Cr-Zr-N alloy coating can be used for surface protection. At this time, the Cr-Zr-N alloy coating is located on the surface of the alloy film product, which can provide a high-brightness surface for the alloy film product; the Cr-Zr-N alloy coating can also be used as an intermediate protective layer. At this time, other structural layers are also provided on the outside of the Cr-Zr-N alloy coating, that is, the Cr-Zr-N alloy coating is not used as a surface layer. The Cr-Zr-N alloy coating of the present invention at different positions can achieve better scratch resistance and better corrosion resistance.
[0051] The preparation method of the Cr-Zr-N alloy coating provided by the present invention is simple, easy to operate, green and environmentally friendly, and also has the advantages of being quantifiable, highly efficient and highly repeatable, and is suitable for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work. It should also be noted that the drawings are all drawn in a simplified form and are only used to conveniently and clearly assist in explaining the present invention. The various sizes of each component shown in the drawings are arbitrarily shown and may be accurate or may not be drawn according to the actual scale. For example, in order to make the illustration clearer, the size of the components is appropriately exaggerated in some places in the drawings. Unless otherwise specified, the components in the figure are not drawn to scale. The present invention does not limit each size of each component.
[0053] In the following description, the same reference numerals denote the same parts.
[0054] Figure 1 A schematic structural diagram of an alloy film product comprising the Cr-Zr-N alloy material of the present application in one embodiment of the present invention, including a substrate and a Cr-Zr-N alloy coating of the present application;
[0055] Figure 2 Schematic diagrams of the structures of alloy film products in several embodiments of the present invention; (A) includes a substrate, a transition layer and a Cr-Zr-N alloy coating of the present invention; (B) includes a substrate, a transition layer, a Cr-Zr-N alloy coating of the present invention and a surface layer; (C) includes a substrate, a Cr-Zr-N alloy coating of the present invention and a surface layer;
[0056] Figure 3A schematic diagram of a device for preparing a Cr-Zr-N alloy coating of the present application in one embodiment of the present invention;
[0057] Figure 4 The Cr prepared in Example 1 of the present invention 81.6 Zr 13.7 N 4.7 SEM cross-sectional image of the alloy coating;
[0058] Figure 5 The Cr prepared in Example 1 of the present invention 81.6 Zr 13.7 N 4.7 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;
[0059] Figure 6 The Cr prepared in Example 2 of the present invention 61.4 Zr 33.2 N 5.4 SEM cross-sectional image of the alloy coating;
[0060] Figure 7 The Cr prepared in Example 2 of the present invention 61.4 Zr 33.2 N 5.4 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;
[0061] Figure 8 The Cr prepared in Example 3 of the present invention 47.1 Zr 17.4 N 35.5 SEM cross-sectional image of the alloy coating;
[0062] Fig. 9 The Cr prepared in Example 3 of the present invention 47.1 Zr 17.4 N 35.5 XRD diffraction pattern of alloy coating;
[0063] Fig.10 The Cr prepared in Example 4 of the present invention 52.0 Zr 12.1 N 35.9 SEM cross-sectional image of the alloy coating;
[0064] Fig.11 The Cr prepared in Example 4 of the present invention 52.0 Zr 12.1 N 35.9 XRD diffraction pattern of alloy coating;
[0065] Fig.12 The Cr prepared in Example 5 of the present invention 60.9 Zr 26.1 N 13 SEM cross-sectional image of the alloy coating;
[0066] Fig.13 The Cr prepared in Example 5 of the present invention 60.9 Zr 26.1 N 13 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;
[0067] Fig.14 The Cr prepared in Example 6 of the present invention 60.9 Zr 26.1 N 13 SEM cross-sectional image of the alloy coating, the Cr-Zr-N alloy coating is used as the lower layer of the double-layer structure coating, and there is a titanium nitride coating (as the surface layer) above the alloy coating;
[0068] Fig.15 The Cr prepared in Example 7 of the present invention 60.9 Zr 26.1 N 13 The SEM cross-sectional view of the alloy coating shows that a Cr layer (as a transition layer) in contact with the Cr-Zr-N alloy coating is disposed between the substrate and the Cr-Zr-N alloy coating, and a titanium nitride coating (as a surface layer) is also present above the Cr-Zr-N alloy coating; the alloy film product has a sandwich structure protection structure, and the Cr-Zr-N alloy coating serves as the middle structural layer of the three-layer structural coating;
[0069] Fig.16 The Cr prepared in Example 13 of the present invention 49.5 Zr 18.0 N 32.5 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;
[0070] Fig.17 The Cr prepared in Comparative Example 1 of the present invention 88.9 Zr 11.1 SEM cross-sectional image of the alloy coating;
[0071] Fig.18 The Cr prepared in Comparative Example 2 of the present invention 37.8 Zr 16.2 N 46 SEM cross-sectional image of the alloy coating;
[0072] Fig.19The Cr prepared in Comparative Example 2 of the present invention 37.8 Zr 16.2 N 46 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;
[0073] Fig. 20 The Cr prepared in Comparative Example 4 of the present invention 39.6 Zr 19.4 N 41 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating.
[0074] In the XRD diffraction pattern, the horizontal axis is 2θ, the unit is °, and the vertical axis is the X-ray diffraction intensity (intensity), the unit is au; according to the selected area electron diffraction pattern (SAED) of the alloy coating, the corresponding radial intensity profile is obtained, which is expressed in the form of characteristic atomic spacing (d)-diffraction intensity, with d as the horizontal axis, the unit is angstrom The vertical axis is the electron diffraction intensity (intensity), and the unit is au.
[0075] In the XRD diffraction pattern and the radial intensity profile corresponding to the SAED pattern, au has a well-known meaning in the art.
[0076] In some SEM images, when preparing the cross-section samples to be tested, some cross-section delamination occurs when the silicon wafer is brittle, but it does not affect the observation and analysis of the cross-section morphology. The positions of different structural layers in the substrate and protective coating can be determined according to the thickness of the corresponding structural layers. Fig.14 and Fig.15 Structural layer position markers in .
[0077] Description of reference numerals: 1 is a vacuum chamber, 2 is a sample stage, 3 is a DC anode, 4 is a chromium target (also referred to as a Cr target, specifically a Cr target with radio frequency-assisted DC cathode power generation), and 5 is a zirconium target (also referred to as a Zr target, specifically a Zr target with radio frequency-assisted DC cathode power generation);
[0078] 100 is a substrate, 200 is a transition layer (also called a transition film layer), 300 is the Cr-Zr-N alloy coating of the present application, and 400 is a surface layer (also called a surface film layer). DETAILED DESCRIPTION
[0079] The present invention will be further described in detail below in conjunction with the accompanying drawings, embodiments and examples. It should be understood that these embodiments and examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. The purpose of providing these embodiments and examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive. It should also be understood that the present invention can be implemented in many different forms and is not limited to the embodiments and examples described herein. Those skilled in the art can make various changes or modifications without violating the connotation of the present invention, and the equivalent forms obtained also fall within the protection scope of the present invention. For example, the features described or described as part of an embodiment can be combined in another embodiment in a suitable manner to produce a new embodiment. In addition, in the description below, a large number of specific details are given in order to provide a more comprehensive understanding of the present invention. It should be understood that the present invention can be implemented without one or more of these details.
[0080] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing implementation modes and embodiments and are not intended to limit the present invention.
[0081] the term
[0082] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:
[0083] The terms "and / or", "or / and", and "and / or" used herein include any one of two or more related listed items, and also include any and all combinations of the related listed items, which include any combination of any two related listed items, any more related listed items, or all related listed items. For example, "A and / or B" includes three parallel solutions: A, B, and "a combination of A and B".
[0084] In the present invention, "plurality", "multiple", "multiple times", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0085] In the present invention, unless otherwise specified, "one or more" means any one of the listed items or any combination of the listed items. Similarly, "one or more" and other expressions that mean "one or more" are also understood in the same way unless otherwise specified.
[0086] As used herein, "combination thereof", "any combination thereof", "any combination thereof" etc. include all suitable combinations of any two or more of the listed items.
[0087] Herein, the “suitable” mentioned in “suitable combination”, “suitable method”, “any suitable method”, etc., shall be based on the ability to implement the technical solution of the present invention, solve the technical problem of the present invention, and achieve the expected technical effect of the present invention.
[0088] Herein, "preferred", "better", "more preferred" and "suitable" are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of the present invention. If multiple "preferred" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "preferred" item is independent.
[0089] In the present invention, "further", "further", "particularly", "for example", "such as", "example", "for example", etc. are used for descriptive purposes, indicating that the previous and subsequent different technical solutions are related in terms of the contents covered, but should not be understood as limiting the previous technical solution, nor can they be understood as limiting the scope of protection of the present invention. In the present invention, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0090] In the present invention, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If multiple "optional" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent of each other. In this application, descriptions such as "optionally contain", "optionally include", etc. mean "contain or not contain". "Optional component X" means that component X exists or does not exist.
[0091] In the present invention, in the "first aspect", "second aspect", "third aspect", "fourth aspect", etc., the terms "first", "second", "third", "fourth", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0092] As used herein, the terms "comprising", "including" and "comprising" are synonymous and are inclusive or open-ended and do not exclude additional, unrecited members, elements or method steps.
[0093] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0094] In the present invention, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers in the numerical interval, including the two endpoint integers of the numerical range, and each integer between the two endpoints, is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical ranges disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.
[0095] In this article, unless otherwise specified, "about" means within a certain range above or below the number, and the fluctuation range may vary depending on the type and value of the number. For example, fluctuations within the range of ±2%, ±1%, ±0.5%, etc. of the number are allowed. For example, about 2° can be selected from 2°±0.02°, etc.
[0096] The temperature parameters in the present invention, if not specifically limited, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the precision range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0097] In the present invention, the term "room temperature" generally refers to 4°C to 35°C, such as 20°C ± 5°C. In some embodiments of the present invention, "room temperature" refers to 10°C to 30°C. In some embodiments of the present invention, "room temperature" refers to 20°C to 30°C.
[0098] In the present invention, the term "normal temperature" generally refers to 20°C to 35°C, for example, 20°C to 35°C. In some embodiments of the present invention, "normal temperature" refers to 30°C to 35°C. In some embodiments of the present invention, "normal temperature" refers to 30°C.
[0099] In the present invention, when it comes to the unit of the data range, if there is a unit only after the right endpoint, it means that the units of the left endpoint and the right endpoint are the same. For example, 3-5h means that the units of the left endpoint "3" and the right endpoint "5" are both h (hours).
[0100] All documents mentioned in the present invention are cited as references in this application, just as each document is cited as a reference separately. Unless they conflict with the invention purpose and / or technical solution of the present application, the cited documents involved in the present invention are cited with all contents and all purposes. When the present invention involves cited documents, the definitions of relevant technical features, terms, nouns, phrases, etc. in the cited documents are also cited. When the present invention involves cited documents, the examples and preferred embodiments of the cited relevant technical features may also be incorporated into this application as references, but are limited to the ability to implement the present invention. It should be understood that when the content of the citation conflicts with the description in this application, the present application shall prevail or be modified adaptively according to the description of this application.
[0101] The mass or weight of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the proportional relationship of the mass or weight between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the mass or weight described in the description of the embodiments of the present invention may be units known in the chemical industry such as μg, mg, g, and kg.
[0102] In the present invention, if there are multiple steps involved in the method flow, unless otherwise specified herein, there is no strict order restriction on the execution of these steps, and they can be executed in other orders than described. Moreover, any step can include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be executed in turn, alternating or simultaneously with other steps or parts of sub-steps or stages of other steps.
[0103] When describing positional relationships, unless otherwise specified, when an element such as a layer, film, or substrate is referred to as being "on" another film layer, it can be directly on the other film layer or there can be an intermediate film layer. Further, when a layer is referred to as being "under" another layer, it can be directly below or there can be one or more intermediate layers. It is also understood that when a layer is referred to as being "between" two layers, it can be the only layer between the two layers, or there can be one or more intermediate layers.
[0104] Where “including,” “having,” and “comprising” are used herein, it is intended to cover a non-exclusive inclusion, and another component may also be added unless explicit limiting terms such as “only,” “consisting of,” etc. are used.
[0105] Unless mentioned to the contrary, terms in the singular may include plural forms and should not be construed as being one in number.
[0106] Traditional Cr-Zr-N alloy coatings are usually nanocrystalline and have a high content of columnar crystals. On the one hand, the L value of these alloy coatings is often difficult to achieve a high value, usually about 55 to 65. On the other hand, the high content of columnar crystals in these alloy coatings will promote the formation of a highly ordered structure arranged in a directional manner. The presence of a large number of crystals in the highly ordered structure will lead to gap defects between crystals, which are mainly manifested as penetrating columnar gaps. There are shadows between the columnar crystals in the corresponding scanning electron microscope (SEM) cross-sectional diagram. These penetrating columnar gaps may be one of the important factors leading to poor corrosion resistance of the alloy coating. The inventor of the present application speculates that the traditional directional ordered structure easily leads to an insufficiently dense coating. Under corrosive conditions, the corrosive medium can quickly penetrate the coating through the penetrating gaps and react with the substrate, resulting in poor corrosion resistance of the alloy coating.
[0107] In addition, the alloy materials on the market are currently mainly protected by means of anodic oxidation, magnetron sputtering, etc. For example, aluminum alloys are mainly protected by anodic oxidation, and its working principle is: the aluminum alloy material is placed in a strong acid or strong alkali solution to form oxides and metal and alloy coatings on the surface to form surface protection; because the solution is a strong acid or strong alkali, the product formed by this method is not glossy enough and has a low hardness. In addition, a large amount of wastewater, waste liquid and waste gas are generated during the production process, which is not good for the environment.
[0108] Based on this, in the first aspect of the present invention, a Cr-Zr-N alloy material is provided, the chemical formula of the Cr-Zr-N alloy material is (Cr x Zr y N z )M a , M is a doping element, wherein x, y, z and a are each independently an atomic ratio, 47.1≤x≤81.6, 12.1≤y≤33.2, 4.7≤z≤35.9, and 0≤a / (x+y+z+a)≤0.05. The Cr-Zr-N alloy material can simultaneously provide a Cr-Zr-N alloy coating having a high brightness surface and excellent corrosion resistance, and can be used to prepare an alloy film product having the Cr-Zr-N alloy coating of the present application.
[0109] The Cr-Zr-N alloy material provided by the present invention can also be recorded as "Cr-Zr-N alloy material of this application", "Cr-Zr-N alloy material of this application", "Cr-Zr-N alloy material described in this application", "Cr-Zr-N alloy material of the present invention", "Cr-Zr-N alloy material of the present invention", "Cr-Zr-N alloy material of the present invention", "Cr-Zr-N alloy material provided in this application" or "Cr-Zr-N alloy material described in the present invention", and includes but is not limited to the Cr-Zr-N alloy material provided in the first aspect.
[0110] In the present invention, unless otherwise specified, "Cr-Zr-N alloy" and "CrZrN alloy" both refer to alloys containing Cr, Zr and N elements, and other alloying elements may be contained, and the two can be used interchangeably.
[0111] In the present invention, unless otherwise specified, "Cr-Zr-N alloy material" refers to an alloy material containing Cr, Zr and N elements. Among them, in the Cr-Zr-N alloy material provided by the present invention, the three elements Cr, Zr and N have the above-mentioned specific atomic ratio x:y:z. In the present invention, the form of the Cr-Zr-N alloy material is not particularly limited, and can be, but not limited to, an alloy coating form.
[0112] In the present invention, unless otherwise specified, the "atomic ratio" of two or more elements means the atomic number ratio.
[0113] In the present invention, unless otherwise specified, "Cr-Zr-N ternary alloy" and "CrZrN ternary alloy" both refer to an alloy composed of three elements: Cr element, Zr element and N element.
[0114] The Cr-Zr-N alloy material provided by the present invention mainly comprises three elements: Cr, Zr and N, and these three elements have a specific relative atomic ratio (Cr x Zr y N z ): 47.1≤x≤81.6, 12.1≤y≤33.2 and 4.7≤z≤35.9, so that the Cr-Zr-N alloy material has the ability to form highly disordered distribution and fully dense arrangement of atoms, and can form a densely structured Cr-Zr-N alloy coating. When the Cr-Zr-N alloy coating of the present invention is located on the surface of the product, it can not only give the product a high-brightness beautiful surface, but also provide excellent corrosion resistance. The protection time of the Cr-Zr-N alloy coating containing the Cr-Zr-N alloy material of the present invention in the salt spray corrosion resistance test is much longer than that of the traditional Cr-Zr-N alloy coating.
[0115] Traditional Cr-Zr-N alloy coatings are usually nanocrystalline and have a high content of columnar crystals. The coating structure usually has a large number of through-holes, which on the one hand leads to poor surface reflection characteristics and low brightness, and on the other hand leads to poor corrosion resistance. The Cr-Zr-N alloy material provided by the present invention can form a dense coating with a "highly disordered and fully densely packed" characteristic structure and contains a very small number of through-holes or non-through-holes; wherein, the three atoms of Cr, Zr, and N with different radii have a special atomic ratio, which is conducive to condensing into a highly disordered state during the deposition process, and then can be tightly stacked in a highly disordered state to form a dense, high-brightness surface with better reflection characteristics, and also promote the alloy coating to grow densely, which can inhibit the formation of continuous and large numbers of through-holes, thereby forming an effective isolation between the substrate and the corrosive environment. In addition, since the Cr-Zr-N alloy coating provided by the present invention contains chromium and zirconium elements, the coating has sufficient self-chemical inertness in a corrosive environment. Based on the Cr-Zr-N alloy material of the present application, a Cr-Zr-N alloy coating can be formed which not only has a highly disordered atomic distribution but also has sufficient dense stacking at the atomic scale, thereby avoiding or reducing the through-going gaps formed due to highly ordered arrangement. The dual characteristics of "highly disordered distribution" and "sufficiently dense stacking" of atoms in the alloy coating make the alloy coating have a highly dense structure, which can provide a high-brightness surface while also having excellent corrosion resistance.
[0116] In the Cr-Zr-N alloy material and Cr-Zr-N alloy coating of the present invention, based on the special atomic ratio of Cr, Zr and N, a high content of Cr is used and Zr and N are introduced, so that Cr and Zr are easy to form a strong bond energy, which is conducive to the rapid growth of the Cr-Zr alloy with a suitable atomic ratio during the deposition process, and the addition of an appropriate amount of nitrogen further promotes the re-nucleation of the Cr-Zr alloy to form the Cr-Zr-N alloy of the present invention, which can improve the brightness and corrosion resistance of the coating by improving the density of the coating nucleation, and can also improve the hardness of the coating. Among them, in terms of atomic size, the radius of the Cr atom is The atomic radius of Zr is The atomic radius of N is The atomic sizes of Cr and Zr are similar, while the atomic size of N is smaller. During the nucleation process, an appropriate amount of small-sized N atoms can penetrate into the pores of large-sized Cr and Zr metal grains with appropriate atomic ratios, achieving a better pore-filling effect and making the atomic arrangement denser. At the same time, it can inhibit the growth defects of the columnar crystal structure of the film, thereby improving the brightness and corrosion resistance of the coating, and can also help to improve the hardness of the coating.
[0117] Cr is a high-brightness metal raw material in the coating material. A higher Cr content can effectively improve the brightness of the alloy coating. At the same time, the Cr-Zr-N alloy material of the present invention can be made into a Cr-Zr-N alloy coating of the present invention with high density, so that the surface reflection characteristics of the coating are further improved. The superposition of these two characteristics makes the coating surface brighter during the colorimetric value measurement process, and the brightness value (i.e., L value) is higher. The L value of the Cr-Zr-N alloy coating of the present invention can be ≥70, and some can be as high as 81 and present a high-brightness silver-white color, which is much higher than the L value of the traditional alloy coating (the traditional L value is about 55-65). The high-brightness coating has an aesthetic effect and excellent decorative properties. When applied to the surface of a substrate (such as pure metals, alloys and other materials), a high-brightness aesthetic effect can be achieved, so that the coating is closer to the base color, and a nearly color-free surface can be achieved. This property makes the Cr-Zr-N alloy coating provided in this application have an excellent decorative effect, which is particularly suitable for (but not limited to) 3C digital products, such as mobile phone components, to achieve a high-brightness metal effect, and can also be used in wearable products, automotive products, sports products and other fields.
[0118] When testing the chromaticity value of the alloy coating, the sample to be tested uses a base material that is suitable for practical application. The L value, a value and b value of the sample can be tested using the CM-3700A-U desktop spectrophotometer produced by Konica Japan. The light receiving system selects the F2 light source, and each sample is tested for 6 matrix points and the average value is taken. Among them, the L value represents the brightness value, the a value represents the red and green chromaticity values, and the b value represents the yellow and blue chromaticity values. The larger the L value, the higher the brightness, indicating that the coating surface is denser. The mechanism is as follows: The spectrophotometer is incident light on the surface of the sample to be tested, forming a reflection, and a reflectivity curve can be obtained. The amplitude of the curve can reflect the density of the material, which can be specifically characterized by the L value. On the basis of the same material, the higher its density, the larger the L value it displays.
[0119] The Cr-Zr-N alloy material provided by the present invention has highly disordered atomic distribution and highly dense atomic arrangement, and can realize dense atomic stacking under highly disordered atomic arrangement, so that the formed Cr-Zr-N alloy coating has a special atomic arrangement of "highly disordered and fully dense", thereby avoiding or reducing the formation of through-holes due to highly ordered arrangement of gaps between grains, so that the alloy coating has a highly dense structure, can present a high-brightness surface with better reflective properties, and can also provide excellent corrosion resistance. The preparation of Cr-Zr-N alloy coating using Cr-Zr-N alloy material can effectively reduce the common defects of traditional crystalline coatings, for example, the through-holes between grains in the columnar crystal structure coating are greatly reduced or disappear, so that the Cr-Zr-N alloy coating is more conducive to dense growth, a flat high-brightness surface is obtained, and the alloy coating is endowed with excellent corrosion resistance.
[0120] In addition, the Cr-Zr-N alloy coating prepared by using the Cr-Zr-N alloy material of the present invention has a dense structure, and while providing excellent corrosion resistance, it can also have high hardness characteristics, better reducing scratches or weakening scratch damage. Further, the Cr-Zr-N alloy coating provided by the present invention can have both high corrosion resistance and high hardness characteristics at a relatively low thickness, which can save raw materials, simplify the process, shorten the production cycle, and significantly reduce costs.
[0121] The Cr-Zr-N alloy coating prepared by using the Cr-Zr-N alloy material of the present invention can be used as the surface layer of the alloy film product, and has both beautiful decorative effect and protective effect. The Cr-Zr-N alloy coating provided by the present invention can also be located between the substrate and the surface layer, and has an excellent protective effect, and can better resist corrosion and scratches.
[0122] In some embodiments, when the proportions of 47.1≤x≤81.6, 12.1≤y≤33.2 and 4.7≤z≤35.9 are satisfied and x+y+z=100, x can be any of the following values or an interval consisting of any two of the following values: 47.1, 52.0, 53.8, 54.8, 60.9, 61.4, 81.6, etc.
[0123] In some embodiments, when the proportions of 47.1≤x≤81.6, 12.1≤y≤33.2 and 4.7≤z≤35.9 are satisfied and x+y+z=100, y can be any of the following values or an interval consisting of any two of the following values: 12.1, 13.0, 13.7, 17.4, 26.1, 30.0, 33.2, etc.
[0124] In some embodiments, when the proportions of 47.1≤x≤81.6, 12.1≤y≤33.2 and 4.7≤z≤35.9 are satisfied and x+y+z=100, z can be any of the following values or an interval consisting of any two of the following values: 4.7, 5.4, 6.2, 10.1, 13.0, 20.2, 25.5, 35.5, 35.9, etc.
[0125] In some embodiments, the sum of x, y and z is 100. In this case, x, y and z correspond to the atomic percentages of the three elements Cr, Zr and N, respectively. In this case, the ratio of the three atoms of Cr, Zr and N is constrained within a more suitable range, so that the formed Cr-Zr-N alloy coating is conducive to obtaining a denser structure, higher brightness and better corrosion resistance. In addition, it is also conducive to improving the hardness of the coating.
[0126] The Cr-Zr-N alloy material and the Cr-Zr-N alloy coating provided by the present invention may contain doping elements or may not contain doping elements, and can be flexibly selected according to the additional functional requirements of the alloy material and / or the alloy coating. It can be understood that in the present invention, when doping elements are contained, the type and doping amount of the doping elements are limited to not affecting the high brightness and corrosion resistance of the Cr-Zr-N alloy coating.
[0127] In the present invention, the chemical formula of the Cr-Zr-N alloy material can be expressed as (Cr x Zr y N z )M a , where x, y and z are each independently atomic ratios and are positive numbers, M is the doping element, and a is the atomic ratio of the M element and is 0 or a positive number. During the nucleation process, N atoms can penetrate into the pores of large-sized Cr and Zr metal grains to achieve a better pore filling effect, making the coating atoms stack more densely, and can also inhibit the growth defects of the thin film columnar crystal structure and improve the corrosion resistance of the coating.
[0128] When a is 0, the Cr-Zr-N alloy material does not contain doping elements, corresponding to the Cr-Zr-N ternary alloy material. When a>0, the Cr-Zr-N alloy material contains doping elements, wherein a / (x+y+z) is numerically equal to the relative atomic percentage of the doping elements relative to Cr, Zr, and N, and a / (x+y+z+a) is numerically equal to the atomic percentage of the doping elements in the Cr-Zr-N alloy material.
[0129] Unless otherwise specified, the Cr-Zr-N alloy material provided by the present invention mainly comprises three elements: Cr, Zr and N. Furthermore, the sum of the atomic ratios of the three elements accounts for ≥95% of the sum of the atomic ratios of all elements in the Cr-Zr-N alloy material (corresponding to 0≤a / (x+y+z+a)≤0.05, such as 0≤a / (x+y+z)≤0.05), further such as ≥98% (corresponding to 0≤a / (x+y+z+a)≤0.02, such as 0≤a / (x+y+z)≤0.02), and further such as Cr-Zr-N ternary alloy material (at this time, a=0). By limiting the content of doping elements, the influence of doping elements on the highly disordered and fully densely packed atoms in the Cr-Zr-N alloy coating of the present application can be minimized, which is beneficial to reducing the elements required for doping or reducing the difficulty of doping, simplifying the preparation process, and promoting the coordinated deposition of Cr, Zr and N to form a denser coating, which is beneficial to achieving better corrosion resistance and obtaining higher hardness.
[0130] In some embodiments, a / (x+y+z)=0. At this time, the Cr-Zr-N ternary alloy material has a simple composition and is easier to prepare and control. The Cr-Zr-N ternary alloy coating formed at this time can obtain a dense structure, can achieve high brightness and high corrosion resistance; in addition, a higher coating hardness can be obtained.
[0131] In some embodiments, 0
[0132] In some embodiments, 0
[0133] In some preferred embodiments, 0
[0134] In some embodiments, based on any of the above suitable embodiments, y is greater than z. At this time, in the Cr-Zr-N alloy material provided by the present invention, the Cr content is relatively high, the Zr content is second, and the nitrogen content is relatively low. This special atomic ratio design can better improve the compactness of the coating nucleation, thereby further improving the brightness value and corrosion resistance of the coating. At this time, during the nucleation process, N atoms can penetrate into the pores of large-sized Cr and Zr metal grains to achieve a better filling effect, making the coating atoms more densely stacked, and can better suppress the growth defects of the columnar crystal structure of the thin film, better improve the surface reflection characteristics of the coating to improve the brightness value, and more significantly improve the corrosion resistance. In addition, it can also promote the realization of better coating hardness.
[0135] In some embodiments, based on any of the above suitable embodiments, 63.19-0.925y≤x≤95.79-y and 31.4+0.9y≤x≤18.5y-171.85. At this time, the three atomic ratios of Cr, Zr and N can be more accurately controlled within a better range, so that the formed Cr-Zr-N alloy coating is conducive to obtaining a denser structure, higher brightness and better corrosion resistance. In addition, it is also conducive to obtaining a better coating hardness.
[0136] In some embodiments, the doping element is a non-metallic element, a metallic element, or a combination thereof, which can be flexibly selected according to the additional functional requirements of the Cr-Zr-N alloy coating.
[0137] Without limitation, the non-metallic element may include one or more of O, C, B, Si and Ar. Without limitation, the metal element may include one or more of Ti, V, Nb, Mo, Hf, Ta, W, Ni, Mo, Fe, Ag, Au, Cu and Al.
[0138] It should be noted that in any embodiment of the present application, the Cr-Zr-N alloy material and Cr-Zr-N alloy coating provided by the present application allow the presence of inevitable impurities introduced during the preparation process. "Inevitable impurities" are not intentionally added impurities, and the main reason for their existence is that they are accidentally introduced during the preparation process; non-limiting examples of "inevitable impurities" include, for example, elements such as C and O present in the air, and may also come from components in raw materials or equipment. The atomic content of "inevitable impurities" in alloy materials or alloy coatings is usually trace or micro, which can generally be ignored, such as less than 0.01% atomic content. Taking the technical solution of "Cr-Zr-N alloy coating is a Cr-Zr-N ternary alloy material composed of Cr, Zr and N elements" as an example, at this time, theoretically, the Cr-Zr-N alloy coating is composed of three elements: Cr, Zr and N, but trace or micro amounts of other elements other than Cr, Zr and N may be introduced during the preparation process, such as C, O, etc.
[0139] In the second aspect of the present invention, a Cr-Zr-N alloy coating is provided, and the Cr-Zr-N alloy coating includes a film layer formed by the Cr-Zr-N alloy material described in the first aspect of the present invention. As mentioned above, based on the special atomic ratio of Cr, Zr, and N, the Cr-Zr-N alloy coating forms a highly disordered atomic distribution and a sufficiently dense atomic arrangement, and has a "highly disordered and sufficiently dense" dense coating structure, thereby improving the surface reflection characteristics and increasing the brightness, and also inhibiting the formation of continuous and large numbers of penetrating gaps, significantly improving the corrosion resistance of the coating.
[0140] In addition, based on the improvement of the density of the coating structure, a higher coating hardness can also be obtained. The Cr-Zr-N alloy coating provided by the present invention has a dense structure, and while providing excellent corrosion resistance, it can also have high hardness characteristics, which can better reduce the generation of scratches or weaken scratch damage. Furthermore, the Cr-Zr-N alloy coating provided by the present invention can have both high corrosion resistance and high hardness characteristics at a relatively low thickness, which can save raw materials, simplify the process, shorten the production cycle, and significantly reduce costs. The Cr-Zr-N alloy coating provided by the present invention can be used as the surface layer of an alloy film product, which has both beautiful decorative effects and protective effects. The Cr-Zr-N alloy coating provided by the present invention can also be located between the substrate and the surface layer, playing an excellent protective role, and can better resist corrosion and scratches.
[0141] In some embodiments, the Cr-Zr-N alloy coating satisfies the following two characteristics:
[0142] The X-ray diffraction pattern of the Cr-Zr-N alloy coating has a peak in the diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of at least one 2θ (°) diffraction peak in the range of 30° to 50° satisfies ≥ 2°;
[0143] In the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy coating, the characteristic atomic spacing is taken as the abscissa and the diffraction intensity is taken as the ordinate. There are diffraction peaks in the range of The half-width of at least one diffraction peak in the range satisfies
[0144]
[0145] The means for structural characterization of the Cr-Zr-N alloy coating in the present invention can also be used to characterize the Cr-Zr-N alloy material of the first aspect of the present invention, and the Cr-Zr-N alloy material may not be limited to the coating form, but may be an independent raw material, such as an alloy sheet, alloy plate, etc.
[0146] For example, in some embodiments, the Cr-Zr-N alloy material satisfies the following two characteristics:
[0147] The X-ray diffraction pattern of the Cr-Zr-N alloy material has a peak within the diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of at least one 2θ (°) diffraction peak within the range of 30° to 50° satisfies ≥ 2°;
[0148] In the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy material, the characteristic atomic spacing is taken as the abscissa and the diffraction intensity is taken as the ordinate. There are diffraction peaks in the range of The half-width of at least one diffraction peak in the range satisfies
[0149]
[0150] Furthermore, the XRD test results of the Cr-Zr-N alloy material and the radial intensity profile results corresponding to the selected area electron diffraction pattern can also refer to the description of the radial intensity profile corresponding to the X-ray diffraction pattern and the selected area electron diffraction pattern in the Cr-Zr-N alloy coating in this article, and the corresponding optional and preferred methods can also be applied to the Cr-Zr-N alloy material.
[0151] The Cr-Zr-N alloy coating provided by the present application is not clearly divided into the traditional perfect single crystal or fully amorphous state, but focuses on the close packing degree of atomic arrangement. Based on the specific atomic ratio of Cr, Zr and N, the close packing degree is closely related to the disorder of atomic arrangement and the appropriate mismatch of atomic size. The highly dense Cr-Zr-N alloy coating provided by the present invention has both high brightness value and excellent corrosion resistance in performance. In addition, high hardness characteristics can be obtained. In terms of structure, it also satisfies the requirements of having at least one broad peak (furthermore, there may be no sharp peak, that is, all are broad peaks) in the diffraction angle 2θ (°) range of 30° to 50° in the XRD diagram and the radial intensity profile of the selected area electron diffraction pattern is There is at least one broad peak in the range (furthermore, there may be no sharp peaks, that is, all are broad peaks).
[0152] Different from the conventional Cr-Zr-N alloy coatings which are nanocrystalline and have a high columnar crystal content (which have a large number of through-type pores), the Cr-Zr-N alloy coating provided by the present invention can form a dense coating having a "highly disordered and fully densely packed" characteristic structure and containing very few through-type pores or no through-type pores. In the Cr-Zr-N alloy coating of the present invention, the three atoms of Cr, Zr, and N with very different radii condense into a highly disordered state during the deposition process and form a dense accumulation to form a dense, high-brightness surface with good reflective properties, so that the alloy coating is easy to grow densely, and the formation of continuous and large numbers of through-type gaps can be suppressed, thereby forming an effective isolation between the substrate and the corrosive environment. In addition, because the Cr-Zr-N alloy coating provided by the present invention contains chromium and zirconium elements, the coating has sufficient self-chemical inertness in a corrosive environment. The Cr-Zr-N alloy material in the alloy coating of the present invention not only has a highly disordered atomic distribution, but also has sufficient dense stacking at the atomic scale, thereby avoiding or reducing penetrating gaps caused by highly ordered arrangement. The dual characteristics of "highly disordered distribution" and "sufficiently dense stacking" of atoms in the alloy coating make the alloy coating have a highly dense structure, which can provide a high-brightness surface and excellent corrosion resistance at the same time.
[0153] In the present invention, whether the constituent atoms of the alloy coating have a "highly disordered" state is evaluated by XRD technology. Specifically, the XRD diagram of the Cr-Zr-N alloy coating shows wide and gentle ridges, and these "wide and gentle ridges" are called "broad peaks" of the 2θ (°) diffraction peak. The length of the orderly arrangement of atoms can be obtained by using the Scherrer formula from the half-height width of the wide peak. The calculation method is: D = Kλ / (β·cosθ), where D is the length of the orderly arrangement of atoms (representing the grain size in crystalline materials), K is the Scherrer constant, λ is the wavelength of X-rays; β is the half-height width of the diffraction peak (referring to the width value at half the height of the diffraction peak, Full Width at Half Maximum, FWHM), and θ is the diffraction angle. It can be seen that the half-height width FWHM is inversely proportional to the length D of the orderly arrangement of atoms, and the shorter the length D of the orderly arrangement of atoms, the higher the disorder of the atomic distribution. Therefore, the half-width (FWHM) of the diffraction peak within a specific range in the XRD diagram can be used to reflect the degree of disordered distribution of atoms: the wider the half-width (FWHM), the shorter the length of the ordered arrangement of atoms, and the more disordered the overall atomic distribution; the aforementioned wide and gently raised "broad peak" can reflect the highly disordered distribution of atoms in the material as a whole.
[0154] Generally speaking, the higher the atomic order, the stronger the crystallinity, the easier it is to form large-sized grains over a long distance, the narrower the diffraction peak in the XRD diagram, and high crystallinity is often accompanied by sharp peaks. In the alloy coating of the present invention, the three atoms of Cr, Zr, and N can be highly disordered in the Cr-Zr-N alloy coating as a whole, so that it appears as a wide and gentle ridge (broad peak) in the XRD diagram of the Cr-Zr-N alloy coating, which is manifested as "at least one peak in the diffraction angle 2θ (°) range of 30° to 50° is a "broad peak".
[0155] In the present invention, unless otherwise specified, the "broad peak" in the XRD pattern can be defined as a half-height width satisfying ≥2°. The half-height width of the broad peak can further be ≥2.19°, further ≥2.2°, further ≥2.3°, further ≥3°, further ≥3.5°, further ≥4°, further ≥5°. The half-height width of any "broad peak" in the XRD diagram can independently be any of the following values, can be greater than or equal to any of the following values, can be greater than or equal to any of the following values (except 10°) and less than or equal to 10°, and can also be selected from the interval consisting of any two of the following values: 2°, 2.19°, 2.2°, 2.5°, 3°, 3.5°, 4°, 4.04°, 4.42°, 4.5°, 5°, 5.5°, 6°, 6.5°, 7°, 7.5°, 8.42°, 8.5°, 8.85°, 9°, 9.11°, 9.33°, 9.5°, 10°, etc. As non-limiting examples, any of the following ranges may be selected: 2° to 10°, 2° to 9.5°, 2° to 9.4°, 2.1° to 9.5°, 2.1° to 9.4°, 2.15° to 9.35°, 2.19° to 9.33°, etc.
[0156] In the present invention, unless otherwise specified, a "sharp peak" in an X-ray diffraction (XRD) pattern refers to a diffraction peak with a half-height width < 2°.
[0157] In more detail, in the Cr-Zr-N alloy coating provided by the present application, the XRD pattern has peaks in the diffraction angle 2θ(°) range of 30° to 50°, and at least one of the diffraction peaks in the XRD spectrum is a broad peak. The special microstructural state in which at least one peak is a "broad peak" can be represented by "having at least one 2θ(°) diffraction peak with a half-width ≥2° in the range of 30° to 50°" or "having at least one 2θ(°) diffraction peak with a half-width ≥2° in the range of 30° to 50°". The following method can be used to determine whether "having at least one 2θ(°) diffraction peak with a half-width ≥2° in the range of 30° to 50°" is satisfied: in the XRD spectrum, if the half-width value of the 2θ(°) diffraction peak is ≥2°, it is judged as a "broad peak"; if the half-width value of the 2θ(°) diffraction peak is <2°, it is judged as a sharp peak. For a certain specified 2θ(°) position, it can be any of the three states of no peak, broad peak or sharp peak. In the X-ray diffraction (XRD) diagram, the broad peak characteristics of the characteristic diffraction peak of the Cr-Zr-N alloy coating provided by the present invention are more obvious.
[0158] In the traditional Cr-Zr-N alloy coating with a high content of columnar crystals, the diffraction peak in the diffraction angle 2θ (°) range of 30° to 50° often appears as a sharp peak with a half-height width < 2°, and no broad peak appears.
[0159] In the present invention, conventional instruments and methods in the art can be used to obtain the XRD pattern of the alloy coating, for example, a German Bruker D8 Advance XRD diffractometer can be used.
[0160] In some embodiments, the X-ray diffraction pattern of the Cr-Zr-N alloy coating of the present invention has a peak in the diffraction angle 2θ(°) range of 30° to 50°, and at least one 2θ(°) diffraction peak in the range of 30° to 50° is a broad peak, and the half-width value of the broad peak can be referred to the examples in the context; taking the half-width of the broad peak ≥2.19° as an example, at least one 2θ(°) diffraction peak in the range of 30° to 50° satisfies ≥2.19°.
[0161] In some embodiments, the X-ray diffraction pattern of the Cr—Zr—N alloy coating of the present invention has a broad peak within a diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of the broad peak can be found in the examples in the context.
[0162] In some embodiments, the X-ray diffraction pattern of the Cr—Zr—N alloy coating of the present invention has two or more broad peaks within a diffraction angle 2θ (°) range of 30° to 50°, and the half-height widths of these broad peaks can be independently referred to the examples in the context.
[0163] In some embodiments, in the X-ray diffraction pattern of the Cr-Zr-N alloy coating of the present invention, all 2θ(°) diffraction peaks within the diffraction angle 2θ(°) range of 30° to 50° are broad peaks, that is, there are no sharp peaks at this time, and the half-height widths of these broad peaks can be independently referred to the examples in the context.
[0164] In some embodiments, the X-ray diffraction pattern of the Cr-Zr-N alloy coating of the present invention has a peak in the diffraction angle 2θ(°) range of 30° to 50°, and the half-width of the 2θ(°) diffraction peak in the range of 30° to 50° each independently satisfies ≥2°, further can each independently satisfy ≥2.19°, further can each independently satisfy ≥2.2°, further can each independently satisfy ≥2.3°, further can each independently satisfy ≥3°, further can each independently satisfy ≥3.5°, further can each independently satisfy ≥4°, further can each independently satisfy ≥5°.
[0165] In some embodiments, the X-ray diffraction pattern of the Cr-Zr-N alloy coating of the present invention has only one diffraction peak within the diffraction angle 2θ (°) range of 30° to 50°, and the diffraction peak is a broad peak.
[0166] In some embodiments, the X-ray diffraction pattern of the Cr—Zr—N alloy coating is obtained by Cu target Kα radiation.
[0167] In the present invention, the following instruments and methods can be used to obtain the XRD pattern of the alloy coating: using a German BrukerD8 Advance XRD diffractometer, in θ-2θ mode, using Cu target Kα rays, a wavelength λ of 0.15406nm, the X-ray tube is controlled at 40kV and 40mA, the scanning range is 20° to 80°, and precise scanning measurement is performed with a step size of 0.01°.
[0168] The half-width value can be obtained by conventional analysis methods in the art (including but not limited to analysis software provided by the instrument supplier). For example, the step of obtaining the half-width value may include: firstly performing correction processing on the diffraction peak, which may include: smoothing, subtracting the background, removing the Kα2 line, subtracting the instrument broadening, etc., and fitting the diffraction peak with the Pseudo-Voigt function to obtain the half-width value of the diffraction peak.
[0169] The analysis software is not particularly limited. Without limitation, EDP2XRD software (version 1.0.0, copyright by Hongwei Liu, The Australian Center for Microscopy and Microanalysis, The University of Sydney) can be used to process the spectrum data. For example, the following method can be used: first, a scale calibration is performed, and then the center of the diffraction ring transmission spot is determined, and then converted into an XRD spectrum (wherein the electron wavelength is 0.00251 nanometers and the X-ray wavelength is 0.154 nanometers; the diffraction peak is deducted from the straight line background, and then fitted with a Voigt function to obtain the half-height width of the corresponding diffraction peak.
[0170] Regarding the characterization of the degree of atomic density in alloy coatings, traditional XRD patterns cannot be used to characterize it well. This is because: when detecting physical vapor deposition (PVD) films or coatings at the atomic scale (such as diameter <3nm), the XRD method often has insufficient resolution due to the large wavelength of X-rays (>0.1nm), and is not suitable for PVD films or coatings with low order (such as grains or amorphous grains with a diameter <3nm).
[0171] In the present invention, whether the atoms constituting the coating have reached "sufficiently densely packed" is evaluated by the selected area electron diffraction pattern (Selected Area Electron Diffraction, SAED). The electron wave is selected because its wavelength is significantly smaller (<0.01nm), so the resolution is higher. Specifically, if there are only continuous diffraction rings with consistent brightness on the SEAD graph, and the diffraction rings are relatively wide, it indicates that the atoms in the coating are densely packed in a highly random mixed manner. In order to quantitatively characterize, the SAED spectrum can be converted into a characteristic atomic spacing (d)-radial intensity profile, wherein the characteristic atomic spacing (d) is the horizontal coordinate and the diffraction intensity is the vertical coordinate. If the diffraction rings in the SEAD are relatively wide, then correspondingly, the half-height width of the radial intensity profile is relatively wide, reflecting that the atomic arrangement in the alloy coating is densely packed.
[0172] In this application, in terms of atomic size, the Cr atomic radius is The atomic radius of Zr is The atomic radius of N is The three atoms with different diameters have a suitable atomic size mismatch, and under the condition of high random mixing, a fully dense structure can be formed. In the growth process of PVD film or alloy coating, the fully dense stacking of atoms in Cr-Zr-N alloy coating makes the alloy coating easy to grow densely, which can inhibit the formation and growth of columnar crystals originally caused by local ordering, and then make it difficult for continuous through-type pores to form in large quantities. Thus, the half-height width of the radial intensity profile can be used as the characteristic parameter of the fully dense structure of the alloy coating to reflect the dense packing of atoms in the alloy coating. The larger the value of the half-height width, the better the dense packing of atoms in the alloy coating. In short, the present invention adopts the half-height width of the radial intensity profile of SAED as the characteristic parameter of fully dense atomic stacking, which is in line with scientific principles and has scientificity.
[0173] When the half-height width of the radial intensity profile is greater than a certain threshold, the atoms in the coating can be fully densely packed. According to a large number of experimental explorations by the inventors, in the present invention, unless otherwise specified, the half-height width threshold for judging whether the atoms are fully densely packed in the SAED-radial intensity profile is determined as Half-height width When the atoms are fully packed together,
[0174] In the present invention, a transmission electron microscope (TEM) technique may be used to obtain a radial intensity profile of a characteristic atomic spacing (d) of an alloy coating sample.
[0175] In the present invention, the radial intensity profile corresponding to the selected area electron diffraction pattern of the alloy coating can be recorded as a SAED-radial intensity profile, and can also be recorded as a characteristic atomic spacing-intensity quantitative spectrum of the selected area electron diffraction pattern (SAED pattern). The selected area electron diffraction pattern obtained by transmission electron microscopy can be recorded as a TEM selected area electron diffraction pattern, and can also be recorded as a TEM-SAED pattern. The SAED-radial intensity profile obtained by transmission electron microscopy can also be recorded as a TEM-SAED-radial intensity profile.
[0176] In the present invention, the alloy coating (including the Cr-Zr-N alloy coating of the present invention) can be obtained by using conventional instruments and methods in the art, and the corresponding radial intensity profile can be obtained according to the selected area electron diffraction pattern (SAED) of the alloy coating. It is expressed in the form of characteristic atomic spacing (d)-diffraction intensity, with d as the horizontal coordinate and the unit being angstroms. The vertical axis represents the electron diffraction intensity.
[0177] In the present invention, unless otherwise specified, the half-height width of the diffraction peak in the radial intensity profile of the SAED pattern is It is judged as a broad peak; the half-height width of the diffraction peak For a specific characteristic interatomic distance, it can be any of the three states of no peak, sharp peak or broad peak. In the radial intensity profile, the broad peak characteristics of the characteristic diffraction peak of the Cr-Zr-N alloy coating provided by the present invention are more obvious. Unless otherwise specified, the "broad peak" in the radial intensity profile of the selected area electron diffraction pattern (SAED pattern) refers to the half-height width The diffraction peak of the spectrum is referred to as the half-height width. diffraction peaks.
[0178] In the present invention, the radial intensity profile or SAED-radial intensity profile, unless otherwise specified, can be obtained using TEM technology.
[0179] In the present invention, unless otherwise specified, the “broad peak” in the radial intensity profile corresponding to the SAED pattern can be defined as the half-height width satisfying The half-width of the broad peak can be further Further, you can Further, you can Further, you can Further, you can
[0180] In the present invention, the following transmission electron microscopy (TEM) method can be used (but not limited to) to obtain the half-width at half maximum data in the radial intensity profile corresponding to the selected area electron diffraction pattern:
[0181] TEM test sample preparation: The Helios 5CX model focused ion beam (FIB) of Thermo Fisher Co., Ltd. of the United States was used to thin the sample to obtain an electron transparent, TEM-observable planar sample.
[0182] SAED image acquisition: A Talos F200x transmission electron microscope (TEM) of Thermo Fisher Co., Ltd. of the United States was used with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm to obtain the selected area electron diffraction pattern (SAED) of the sample. Based on the selected area electron diffraction pattern (SAED) image, a radial intensity profile was obtained, and the half-height width value of the diffraction peak was obtained by using the integrated half-height width assignment.
[0183] According to the principle that the half-width of the diffraction peak in the radial intensity profile corresponds to the width of the diffraction ring in the selected area electron diffraction pattern (SAED) pattern, the selected area electron diffraction pattern (SAED) pattern of the alloy coating can be converted into the corresponding radial intensity profile.
[0184] Those skilled in the art know that the larger the width of the diffraction ring in the selected area electron diffraction pattern, the stronger the random mixing degree of the atoms, and the more densely packed the atoms are in the Cr-Zr-N alloy coating of the present invention; the half-width of the diffraction peak in the radial intensity profile is a quantitative indicator of the width of the diffraction ring, and the larger the half-width value, the more densely packed the atoms are.
[0185] In some embodiments, the selected area electron diffraction pattern (SAED) of the Cr-Zr-N alloy coating is obtained using a transmission electron microscope (TEM) characterization technique, with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm.
[0186] In some embodiments, in the radial intensity profile of the selected area electron diffraction pattern of the Cr-Zr-N alloy coating of the present invention, has at least one half-width diffraction peaks.
[0187] In the radial strength cross-sectional diagram of the Cr-Zr-N alloy coating provided by the present invention, The half-height width of the diffraction peak in the range has an upper limit due to the atomic close packing limit. Non-limiting examples of the upper limit are as follows:
[0188] In the present invention, the half-height width of the "broad peak" in the radial intensity profile corresponding to the SAED pattern can be independently any of the following values, can be greater than or equal to any of the following values, can be greater than or equal to any of the following values and less than or equal to the aforementioned upper limit value (such as ), and can also be independently selected from an interval consisting of any two of the following values:
[0189] As a non-limiting example, the half-height width of the "broad peak" in the radial intensity profile corresponding to the SAED pattern can be selected from any of the following ranges:
[0190] etc.
[0191] In some embodiments, in the radial strength profile of the Cr-Zr-N alloy coating of the present invention, The half-height width of the diffraction peak in the range
[0192] In some embodiments, in the radial strength profile of the Cr-Zr-N alloy coating of the present invention, The half-height width of the diffraction peak within the range can be independently any of the following values, can be independently greater than or equal to any of the following values, and can also be independently selected from an interval consisting of any two of the following values: As a non-limiting example, any of the following ranges may be selected:
[0193] wait.
[0194] In some embodiments, the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy coating of the present invention is There is a broad peak in the range, and its half-height width can be found in the examples in the context. For example, the radial intensity profile corresponding to the selected area electron diffraction pattern is At least one diffraction peak in the range satisfies
[0195] In some embodiments, the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy coating of the present invention is There are 2 or more broad peaks in the range, and their half-height widths can be independently determined by referring to the examples in the context.
[0196] In some embodiments, the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy coating of the present invention is All diffraction peaks within the range are broad peaks, and the half-height width of all diffraction peaks meets See also context definition.
[0197] In some embodiments, the characteristic atomic spacing of the Cr-Zr-N alloy coating of the present invention is obtained using TEM diffraction data; wherein, the TEM diffraction test of the alloy coating is performed using an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm.
[0198] In some embodiments, the TEM test uses a mode with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm to obtain a selected area electron diffraction pattern (SAED) of the Cr—Zr—N alloy coating.
[0199] In some embodiments, based on any of the above suitable embodiments, the thickness of the Cr-Zr-N alloy coating is d min ~6μm, where d min It can be selected from 10nm to 50nm, d min It can also be any of the following thicknesses, or a range selected from any two of the following thicknesses: 10nm, 20nm, 25nm, 30nm, 40nm, 50nm, etc.; for example, the thickness of the Cr-Zr-N alloy coating can be 25nm~6μm, 30nm~6μm, 40nm~6μm, 50nm~6μm, 1.0μm~2.5μm, 1.0μm~2.0μm, etc.
[0200] By controlling the Cr-Zr-N alloy coating to have a more appropriate thickness, the corrosion resistance and / or high hardness characteristics of the alloy coating can be better utilized. The thicker the Cr-Zr-N alloy coating is, the more conducive it is to improving the corrosion resistance and / or hardness of the alloy coating.
[0201] The Cr-Zr-N alloy coating provided by the present invention can provide excellent corrosion resistance while also having high hardness characteristics, thereby better reducing the generation of scratches or weakening scratch damage. Furthermore, the Cr-Zr-N alloy coating provided by the present invention can have both high corrosion resistance and high hardness characteristics at a relatively low thickness, which can save raw materials, simplify the process, shorten the production cycle, and significantly reduce costs. Compared with traditional alloy coatings, the Cr-Zr-N alloy coating of the present invention can provide a denser structure, and can achieve better corrosion resistance, high hardness and characteristics at the same thickness, thereby reducing the coating thickness while maintaining better coating protection characteristics, which is beneficial to saving raw materials, simplifying the process, shortening the production cycle, and significantly reducing costs.
[0202] In some embodiments, the Cr—Zr—N alloy coating has a thickness of 10 nm to 6 μm.
[0203] In some embodiments, the Cr—Zr—N alloy coating has a thickness of 25 nm to 6 μm.
[0204] In some embodiments, the Cr—Zr—N alloy coating has a thickness of 1 μm to 2.5 μm.
[0205] In addition, when a relatively thin Cr-Zr-N alloy coating of the present application is formed on a substrate, the formed alloy film product can present a silvery white metallic color, which is close to the metallic color of the substrate, and can achieve a beautiful decorative effect without changing the color of the substrate.
[0206] In a third aspect of the present invention, an alloy film product is provided, which includes a substrate 100 and the Cr-Zr-N alloy coating described in the second aspect of the present invention (that is, the Cr-Zr-N alloy coating 300 of the present application); wherein the Cr-Zr-N alloy coating is located on at least one side of the substrate.
[0207] The alloy film product provided by the present invention includes a film layer formed by the Cr-Zr-N alloy coating of the present application, and is therefore called an alloy film product.
[0208] The Cr-Zr-N alloy coating provided by the present invention can be used as the surface layer of the alloy film product, and has both decorative and protective effects. The Cr-Zr-N alloy coating provided by the present invention can also be located between the substrate and the surface layer, and has an excellent protective effect, and can better resist corrosion and scratches.
[0209] The Cr-Zr-N alloy coating provided by the present invention can be located on one side or both sides of the substrate.
[0210] In some embodiments, the surface material of the substrate is one of an alloy, a single metal and an inorganic non-metallic material. Without limitation, the material type of the alloy may include one or more of a nickel-based, iron-based, tungsten-based, titanium-based, silicon-based, aluminum-based, copper-based, cobalt-based, zirconium-based and zinc-based. Without limitation, the single metal may be any one of zinc, gold, platinum, zirconium, hafnium, niobium, tantalum, nickel, copper, aluminum, iron, silver and chromium. Without limitation, the inorganic non-metallic material may include one or more of ceramics and glass. Without limitation, the inorganic non-metallic material may include a silicon wafer.
[0211] The Cr-Zr-N alloy coating provided by the present invention can be applied to a variety of substrates, and the materials of the substrates include but are not limited to alloys, elemental metals, inorganic non-metallic materials (such as silicon wafers, ceramics, glass) and other substrates.
[0212] In some embodiments, the surface material of the substrate is one of light alloys or one of stainless steel alloys; optionally, the light alloy may include one or more of titanium alloy, aluminum alloy and magnesium alloy.
[0213] In some embodiments, the surface material of the substrate is one of light alloys; further, the light alloy may include one or more of titanium alloy, aluminum alloy and magnesium alloy.
[0214] In some embodiments, the surface material of the substrate is one of stainless steel alloys. Further, the stainless steel alloy can be any one of austenitic stainless steel, ferritic stainless steel, martensitic stainless steel, etc.
[0215] In some embodiments, the alloy film product satisfies one or more of the following characteristics:
[0216] The Cr-Zr-N alloy coating is in direct contact with the substrate (in this case, there is no transition layer) or a transition layer is provided. Further, the transition layer may be a single-layer structure or a multi-layer structure (that is, one or more structural layers may be formed between the Cr-Zr-N alloy coating provided by the present invention and the substrate);
[0217] The Cr-Zr-N alloy coating is located on the surface of the alloy film product or a surface layer is provided on the side of the Cr-Zr-N alloy coating away from the substrate. Furthermore, the surface layer can be a single-layer structure or a multi-layer structure (that is, one or more structural layers can continue to be formed on the Cr-Zr-N alloy coating provided by the present invention).
[0218] In this application, unless otherwise specified, "transition layer" and "transition film layer" have the same meaning and can be used interchangeably. Both refer to a structural layer with transitional properties located between the substrate and the Cr-Zr-N alloy coating described in this application in an alloy film product. It can be a single-layer structure or a multi-layer structure.
[0219] In this application, unless otherwise specified, "surface layer" and "surface film layer" have the same meaning and can be used interchangeably. They both refer to the structural layer of the Cr-Zr-N alloy coating described in this application in the alloy film product that is away from the substrate side and located on the surface of the product. It can be a single-layer structure or a multi-layer structure.
[0220] In some implementations, the Cr—Zr—N alloy coating 300 of the present application is in direct contact with the substrate 100 (in this case, there is no transition layer).
[0221] In some implementations, a transition layer 200 is provided between the Cr—Zr—N alloy coating 300 and the substrate 100 of the present application.
[0222] In some implementations, the Cr—Zr—N alloy coating 300 of the present application is located on the surface of the alloy film product.
[0223] In some implementations, a surface layer 400 is further provided on a side of the Cr—Zr—N alloy coating 300 of the present application away from the substrate 100 .
[0224] Figure 1 A schematic structural diagram of an alloy film product containing the Cr—Zr—N alloy coating of the present application in one embodiment of the present invention is provided, including a substrate 100 and the Cr—Zr—N alloy coating of the present application 300.
[0225] Figure 2 Schematic diagrams of the structures of alloy film products in several embodiments of the present invention are provided: (A) includes a substrate 100, a transition layer 200 and a Cr-Zr-N alloy coating 300 of the present application; (B) includes a substrate 100, a transition layer 200, a Cr-Zr-N alloy coating 300 of the present application and a surface layer 400; (C) includes a substrate 100, a Cr-Zr-N alloy coating 300 of the present application and a surface layer 400.
[0226] When the Cr-Zr-N alloy coating provided by the present invention appears in the protective coating of the alloy film product, the position of the Cr-Zr-N alloy coating can be flexibly set, and it can be used as a protective coating of a single structural layer of the protective coating, or as a layer in a multi-layer structural protective coating. For example, the Cr-Zr-N alloy coating can be used for surface protection. At this time, the Cr-Zr-N alloy coating is located on the surface of the alloy film product, which can provide a high-brightness surface for the alloy film product; the Cr-Zr-N alloy coating can also be used as an intermediate protective layer. At this time, other structural layers are also provided on the outside of the Cr-Zr-N alloy coating, that is, the Cr-Zr-N alloy coating is not used as a surface layer. Different coating position settings can achieve better scratch resistance and better corrosion resistance.
[0227] In some embodiments, the alloy film product is one of 3C digital products, automotive products, aerospace products, wearable products and sports products.
[0228] Without limitation, 3C digital products may include but are not limited to mobile device components, wearable components, vehicle-mounted components, etc.
[0229] According to the difference in the main components of the substrate, the alloy film product can be any one of a light alloy product, a stainless steel product, a single metal, an inorganic non-metallic based product (such as a ceramic based product, a silicon based product, a glass based product), etc., indicating that the main components of the substrate are light alloy, stainless steel, single metal, etc., respectively. Without limitation, light alloy products may include but are not limited to aluminum alloy products, titanium alloy products, magnesium alloy products, etc. Without limitation, stainless steel products may include but are not limited to austenitic stainless steel, ferritic stainless steel, martensitic stainless steel. Without limitation, single metal products may include but are not limited to zinc, gold, platinum, zirconium, hafnium, niobium, tantalum, nickel, copper, aluminum, iron, silver and chromium, further such as copper, aluminum, iron, silver and chromium.
[0230] In one embodiment, the alloy film product is an aluminum alloy product.
[0231] In one embodiment, the alloy film product is a stainless steel product.
[0232] In one embodiment, the alloy film product is an inorganic non-metal-based product, and may further be a silicon-based product, a ceramic-based product or a glass-based product.
[0233] In one embodiment, the alloy film product is a copper product.
[0234] The alloy film product can be an intermediate product or a final product. The final product can be used or sold directly. The intermediate product can be further processed or assembled with other components into a new product.
[0235] In a fourth aspect of the present invention, there is provided an application of the Cr—Zr—N alloy material described in the first aspect of the present invention or the Cr—Zr—N alloy coating described in the second aspect of the present invention.
[0236] As mentioned above, the Cr-Zr-N alloy coating of the present application can be used as a surface layer or can be located between the substrate and the surface layer.
[0237] In some embodiments, the application of the Cr-Zr-N alloy material described in the first aspect of the present invention in preparing a high-brightness surface coating or the application of the Cr-Zr-N alloy coating described in the second aspect of the present invention as a high-brightness surface coating is provided; further, the brightness value L of the high-brightness surface coating is ≥ 70 when tested by the Lab method. In some of the embodiments, the high-brightness surface coating is also a corrosion-resistant protective coating.
[0238] In the present invention, unless otherwise specified, "surface coating" refers to a coating located on the surface of the product, which may be the Cr-Zr-N alloy coating of the present application, or an additional surface layer may be provided on the basis of the Cr-Zr-N alloy coating of the present application.
[0239] When the Cr—Zr—N alloy coating of the present application is located on the surface of a product, it can not only give the product a high-brightness surface, but also provide excellent corrosion resistance.
[0240] The L value of the Cr-Zr-N alloy coating of the present invention can be ≥70, and some can be as high as 81 and present a high-brightness silver-white color, which is much higher than the L value of the traditional alloy coating (the traditional L value is about 55-65).
[0241] In some implementations, when tested by the Lab method, the brightness value L is ≥70, further ≥75, and further ≥80.
[0242] In some embodiments, taking an aluminum alloy substrate as an example, a corrosion-resistant protective coating including the Cr-Zr-N alloy coating of the present application is formed on the surface of the aluminum alloy substrate, and the corrosion-resistant protective coating has a protection time of ≥24 hours in a salt spray corrosion test, that is, it can pass a 24-hour test, and most embodiments can also pass a 48-hour test, using the ASTM B117 salt spray test method; further, a more detailed test method described above or below can be used. Taking an aluminum alloy substrate as an example, under the same test conditions, the protection time of a conventional alloy coating in a salt spray corrosion test is generally difficult to reach 8 hours.
[0243] The Cr-Zr-N alloy coating provided by the present invention can have both excellent corrosion resistance and high hardness characteristics at a relatively low thickness, thereby saving raw materials, simplifying the process, shortening the production cycle, and significantly reducing costs. When the thickness of the alloy coating is relatively thin, the formed alloy film product can present a silvery white metallic color close to the metallic color of the substrate, which is more conducive to achieving a beautiful decorative effect without changing the color of the substrate.
[0244] In the fifth aspect of the present invention, a method for preparing an alloy coating is provided, which comprises the following steps: using vapor deposition technology to deposit the constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of a substrate according to a preset atomic ratio, thereby forming the Cr-Zr-N alloy coating described in the second aspect of the present invention.
[0245] The preparation method of the Cr-Zr-N alloy coating provided by the present invention is simple, easy to operate, green and environmentally friendly, and also has the advantages of being quantifiable, highly efficient and highly repeatable, and is suitable for industrial application.
[0246] The definition of the substrate may be incorporated into the third aspect of the present invention.
[0247] In some embodiments, the vapor deposition technique is a physical vapor deposition technique. Further, the physical vapor deposition technique can be implemented by one or more of the following methods: vacuum evaporation, sputtering, arc plasma plating, ion plating, and molecular beam epitaxy.
[0248] In one embodiment, the physical vapor deposition method is magnetron sputtering coating.
[0249] In some embodiments, sputtering coating (such as magnetron sputtering coating) technology is used to deposit the constituent elements of the Cr—Zr—N alloy coating on at least a portion of the surface of the substrate according to a preset atomic ratio.
[0250] In some embodiments, see Figure 3 The device shown. Figure 3 The device shown includes a vacuum chamber 1, a sample stage 2, a DC anode 3, a chromium target 4 and a zirconium target 5; wherein the chromium target 4 is a chromium target with radio frequency assisted DC cathode power supply, and the zirconium target 5 is a zirconium target with radio frequency assisted DC cathode power supply. The figure is not drawn in a 1:1 ratio, and the relative sizes of the components are drawn in the figure only as examples to facilitate the understanding of the present invention, but are not necessarily drawn in true proportions, and the proportions in the figure do not constitute a limitation of the present invention. The Cr-Zr-N alloy coating of the present invention can be formed by reactive sputtering with a N2-containing gas (such as an Ar / N2 mixed gas) in the vacuum chamber 1.
[0251] In some embodiments, the preparation method of the Cr-Zr-N alloy coating comprises the following steps: under the condition of introducing a mixed gas containing argon and a nitrogen-containing gas, using one or more targets including chromium and zirconium, sputtering and depositing the constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of the substrate to form the Cr-Zr-N alloy coating. The nitrogen-containing gas may be, but is not limited to, nitrogen. At this time, the gas ratio of argon and nitrogen in the mixed gas may be (2-6):1, for example, 2:1, 3:1, 4:1, 5:1, 6:1, etc. When nitrogen is selected as the nitrogen-containing gas and the nitrogen content is controlled to a certain level, the performance of the Cr-Zr-N alloy coating of the present invention can be further adjusted.
[0252] The target material may include one or more of a chromium target, a zirconium target and an alloy target. The alloy target includes at least two metal elements in the Cr-Zr-N alloy coating. The atomic ratio of the metal elements in the alloy target may be the same as or close to the atomic ratio of the corresponding metal elements in the Cr-Zr-N alloy coating. In some embodiments, the alloy target is a chromium-zirconium-based alloy target, wherein the chromium-zirconium-based alloy target includes at least chromium and zirconium, such as a CrZr alloy target, a CrZrN alloy target, and the like. In some embodiments, the atomic ratio of Cr and Zr in the chromium-zirconium-based alloy target is 65%:35%. In some embodiments, the alloy target includes all metal elements in the Cr-Zr-N alloy coating. Examples of alloy targets can be found in Example 2 below.
[0253] In the present invention, unless otherwise specified, a "chromium-zirconium-based alloy target" includes at least chromium and zirconium, and may include or exclude other elements. When other elements are included, it is understood that the chemical composition of the target material should generally be within the preset chemical formula (Cr x Zr y N z )M a For example, the chromium-zirconium-based alloy target may be a chromium-zirconium-nitrogen alloy target (ie, a CrZrN alloy target) composed of three elements: chromium, zirconium, and nitrogen.
[0254] In some embodiments, a chromium-zirconium alloy target is used, which can be replaced Figure 3 Medium chromium target 4, installed on Figure 3 The location of Zhongyuan chromium target 4.
[0255] In some embodiments, the preparation method of the Cr-Zr-N alloy coating, taking a sputtering coating method (such as a magnetron sputtering coating) method as an example, comprises the following steps: under the condition of introducing a mixed gas comprising argon and a nitrogen-containing gas, using a chromium target and a zirconium target or a chromium-zirconium alloy target (i.e., a CrZr alloy target), sputtering and depositing the constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of the substrate to form the Cr-Zr-N alloy coating.
[0256] In some embodiments, before the step of "sputtering and depositing the constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of the substrate", the following step is also included: cleaning the substrate. The method for cleaning the substrate can adopt a conventional cleaning method in the technical field (including but not limited to the field of decorative plating).
[0257] In some embodiments, the cleaning treatment of the substrate includes the following steps: placing the substrate in water for ultrasonic cleaning for 10-15 minutes, vacuum drying the cleaned substrate for 15-20 minutes, and placing the substrate on a sample stage of a sputtering coating (such as magnetron sputtering coating) device after drying. The sample stage may be a rotatable sample stage.
[0258] In one embodiment, the cleaning process of the substrate includes the following steps: placing the substrate in deionized water (DI water) for ultrasonic cleaning for 10-15 minutes, placing the cleaned substrate in a vacuum baking oven for baking for 15-20 minutes, and placing the substrate on a rotatable sample table in a vacuum chamber after drying.
[0259] In some embodiments, after the step of "cleaning the substrate", before the step of "sputtering and depositing the constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of the substrate", the following step is also included: forming a transition layer (the transition layer can serve as a buffer film) on at least a portion of the surface of the cleaned substrate. For example, the constituent elements of the transition layer can be deposited on at least a portion of the surface of the cleaned substrate.
[0260] In some embodiments, after the Cr—Zr—N alloy coating of the present invention is formed on one side of the substrate, further deposition may be performed to form a surface layer, and the surface layer may be a single-layer structure or a multi-layer structure.
[0261] In some embodiments, the temperature of sputtering deposition is 30°C to 330°C, for example, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 150°C, 200°C, 250°C, 300°C, 330°C, etc.
[0262] In some embodiments, the total gas pressure of the mixed gas comprising argon gas and nitrogen-containing gas is 0.3 Pa to 1.2 Pa; for example, 0.3 Pa, 0.5 Pa, 0.8 Pa, 1 Pa, 1.2 Pa, etc.
[0263] In some embodiments, sputtering is performed by radio frequency assisted direct current sputtering, which can further improve the performance of the alloy coating formed by sputtering deposition compared to other preparation methods.
[0264] In some embodiments, the target material includes a chromium target, and the power density of the chromium target is 3.5 W / cm 2 ~6.7W / cm 2 .
[0265] In some embodiments, the target material comprises a zirconium target, and the power density of the zirconium target is 0.5 W / cm 2 ~3.0W / cm 2 .
[0266] In some embodiments, the target material includes a chromium target and a zirconium target, and the power density of the chromium target is 3.5 W / cm 2 ~6.7W / cm 2 , and the power density of the zirconium target is 0.5W / cm 2 ~3.0W / cm 2 .
[0267] In some embodiments, the target material comprises an alloy target, and the alloy target comprises at least two metal elements in the Cr-Zr-N alloy coating; optionally, the target material comprises a chromium-zirconium-based alloy target, and the power density of the chromium-zirconium-based alloy target is 4W / cm 2~6W / cm 2 .
[0268] In some embodiments, the target material includes the chromium-zirconium alloy target, and the power density of the chromium-zirconium alloy target is 5 W / cm 2 .
[0269] In some embodiments, the target material is a chromium-zirconium alloy target with a power density of 4 W / cm 2 ~6W / cm 2 , 5W / cm2 is optional 2 .
[0270] In some embodiments, the bias voltage of the substrate is -150 V to -20 V; for example, -150 V, -120 V, -100 V, -90 V, -80 V, -60 V, -50 V, -40 V, -30 V, -20 V, etc.
[0271] In some embodiments, the gas flow rate of the nitrogen-containing gas may be 5 sccm to 52 sccm, such as 5 sccm, 10 sccm, 20 sccm, 25 sccm, 30 sccm, 40 sccm, 50 sccm, 52 sccm, etc. Further, the nitrogen-containing gas is nitrogen gas.
[0272] In some embodiments, the sputtering deposition time is 10 min to 150 min, for example, 10 min, 15 min, 30 min, 45 min, 60 min, 90 min, 100 min, 120 min, etc. The thickness of the Cr-Zr-N alloy coating of the present invention can be controlled by adjusting the deposition time. As the deposition time increases, the thickness of the Cr-Zr-N alloy coating increases.
[0273] In some embodiments, the background vacuum of the vacuum chamber used is ≤5.0×10 -4 Pa. This pressure setting can ensure the collision between the sputtered particles and the gas molecules, and can also reduce the entry of impurities into the gas molecules during the deposition process, so as to improve the corrosion resistance, purity and bonding strength of the Cr-Zr-N alloy coating of the present invention.
[0274] It can be understood that argon gas and nitrogen-containing gas can be introduced into the vacuum chamber through a single path or mixed through a mixing cylinder and then enter the chamber, thereby reducing the impurity content of the Cr-Zr-N alloy coating of the present invention and improving its performance.
[0275] In some embodiments, "using sputtering coating (such as magnetron sputtering coating) technology to load the constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of the substrate according to a preset atomic ratio" includes the following steps: introducing a mixed gas containing argon and nitrogen-containing gas into the vacuum chamber 1, maintaining the pressure in the vacuum chamber 1 at 0.5Pa to 0.8Pa, turning on the bias voltage and setting it to -150V to -20V, setting the power density of the chromium target 4 to 3.5W / cm 2 ~6.7W / cm 2 , the power density of zirconium target 5 is set to 0.5 W / cm 2 ~3.0W / cm 2 , a Cr-Zr-N alloy coating is deposited on at least a portion of the surface of the substrate after cleaning; further, the Cr-Zr-N alloy coating with different film thicknesses can be obtained by controlling the film forming time.
[0276] Some specific embodiments are provided below.
[0277] The embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are preferably referred to the guidance provided in the present invention, and can also be based on the experimental manual or normal conditions in this area, can also be based on the conditions recommended by the manufacturer, or refer to experimental methods known in the art.
[0278] In the following specific embodiments, the measured parameters of raw material components may have slight deviations within the range of weighing accuracy unless otherwise specified. For temperature and time parameters, acceptable deviations caused by instrument test accuracy or operation accuracy are allowed.
[0279] Test method:
[0280] 1. Chroma value test of alloy coating
[0281] When testing the chromaticity value of the alloy coating, the sample to be tested uses a substrate that is suitable for practical application, and detects the degree of improvement of the compactness and other properties of the substrate by the alloy coating. The surface material of the "substrate that is suitable for practical application" may include but is not limited to: aluminum alloy, stainless steel.
[0282] The L value, a value and b value of the samples were tested using a CM-3700A-U desktop spectrophotometer produced by Konica Japan. The F2 light source was selected as the light receiving system. Six matrix points were tested for each sample and the average value was taken.
[0283] Among them, the L value represents the brightness value, the a value represents the red and green chromaticity values, and the b value represents the yellow and blue chromaticity values.
[0284] The larger the L value, the higher the brightness, indicating that the coating surface is denser. The mechanism is as follows: the spectrophotometer reflects the incident light on the surface of the sample to be tested, and a reflectance curve is obtained. The amplitude of the curve can reflect the density of the material, which can be specifically characterized by the L value. For the same material, the higher its density, the larger the L value it displays.
[0285] 2. Morphology and composition test analysis of alloy coating
[0286] The samples to be tested all use silicon wafers as substrates.
[0287] Scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX) testing methods
[0288] Morphology analysis: A scanning electron microscope (Regulus 8230, manufactured by Hitachi) was used.
[0289] Composition analysis: An energy dispersive X-ray spectrometer (EDX) attached to a Regulus 8230 scanning electron microscope produced by Hitachi was used, and the relative intensities of all elements were corrected by the ZAF method.
[0290] Test parameters: the electron acceleration voltage is 15 kilovolts, the beam current is 10 microamperes, the sample magnification is 200 times, and 10 points are tested for each sample to take the average value.
[0291] 3. X-ray diffraction (XRD) test of alloy coating
[0292] When conducting XRD testing of alloy coatings, silicon wafers were used as substrates.
[0293] 3.1. Calculation of the half-height width of the diffraction peak in the XRD pattern
[0294] A German Bruker D8 Advance XRD diffractometer was used in the θ-2θ mode with Cu target Kα rays, a wavelength λ of 0.15406 nm, the X-ray tube controlled at 40 kV and 40 mA, a scanning range of 20° to 80°, and precise scanning measurements with a step size of 0.01°.
[0295] The steps for obtaining the half-width value are as follows: first, the diffraction peak is corrected, including: smoothing, background subtraction, removal of Kα2 line, subtraction of instrument broadening, etc., and the half-width value of the diffraction peak is obtained after fitting the diffraction peak with the Pseudo-Voigt function.
[0296] The EDP2XRD software (version 1.0.0, copyright by Hongwei Liu, The Australian Center for Microscopy and Microanalysis, The University of Sydney) was used to process the spectrum data: first, the scale was calibrated, then the center of the diffraction ring transmission spot was determined, and then converted into an XRD spectrum (where the electron wavelength is 0.00251 nanometers and the X-ray wavelength is 0.154 nanometers; the diffraction peak was deducted from the straight line background, and then fitted with the Voigt function to obtain the half-height width of the corresponding diffraction peak.
[0297] 3.2. Determine whether the XRD pattern of the alloy coating forms a broad peak
[0298] Method for judging whether there are broad peaks (sharp peaks) in the diffraction angle range of 2θ (°) from 30° to 50° in the XRD diffraction pattern: in the XRD spectrum, if the half-height width of the 2θ (°) diffraction peak is ≥2°, it is judged as a broad peak; if the half-height width of the 2θ (°) diffraction peak is <2°, it is judged as a sharp peak.
[0299] For a given 2θ(°) position, it can be any of the three states: no peak, sharp peak or broad peak.
[0300] 4. TEM test
[0301] When conducting TEM tests on alloy coatings, silicon wafers were used as substrates.
[0302] 4.1. The half-width at half maximum of the diffraction ring of the TEM diffraction pattern is obtained by the following method:
[0303] TEM test sample preparation: The Helios 5CX model focused ion beam (FIB) of Thermo Fisher Co., Ltd. of the United States was used to thin the sample to obtain an electron transparent, TEM-observable planar sample.
[0304] SAED image acquisition: A Talos F200x transmission electron microscope (TEM) produced by Thermo Fisher Scientific Inc., USA, with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm, was used to obtain the selected area electron diffraction pattern (SAED) of the sample.
[0305] Acquisition of radial intensity profile: The SAED spectrum data obtained above were processed using EDP2XRD software (version 1.0.0, copyright by Hongwei Liu, The Australian Center for Microscopy and Microanalysis, The University of Sydney): first, the scale was calibrated, then the center of the diffraction ring transmission spot was determined, and finally, it was converted into a radial intensity profile (where the electron wavelength is 0.00251 nanometers and the X-ray wavelength is 0.154 nanometers), with the characteristic atomic spacing as the horizontal axis and the diffraction intensity as the vertical axis.
[0306] The steps for obtaining the half-width value are as follows: subtract a straight line from the diffraction peak, and then fit it with the Voigt function to obtain the half-width value of the corresponding diffraction peak.
[0307] 4.2. Determine the radial intensity profile of the TEM selected area electron diffraction pattern Method to determine whether there is a broad peak within the range: the half-height width of the diffraction peak corresponding to the characteristic atomic spacing It is judged as a broad peak; the half-height width of the diffraction peak corresponding to the characteristic atomic spacing is For a specific characteristic interatomic distance, it can be any of the three states: no peak, sharp peak or broad peak.
[0308] 5. Salt spray corrosion resistance test of alloy coating
[0309] When the salt spray corrosion resistance test of the alloy coating is carried out, the sample to be tested is a substrate suitable for practical application, and the improvement degree of the corrosion resistance of the substrate by the alloy coating is detected. The surface material of the "substrate suitable for practical application" may include but is not limited to: aluminum alloy, stainless steel.
[0310] The ASTM B117 salt spray test standard is adopted, the pH value of the solution is 6.5-7.2, and the chemical composition of the solution is: sodium chloride (NaCl), deionized water and sodium hydroxide (NaOH).
[0311] 12 hours can be used as a sub-cycle of the salt spray corrosion resistance test.
[0312] The test cycle of alloy coatings prepared on substrates of different materials can be different, for example:
[0313] The test cycle for samples containing aluminum alloy matrix is 48h or 24h;
[0314] The test cycle of stainless steel substrate samples is 144h or 96h;
[0315] The test cycle of the copper sheet substrate sample is 12h.
[0316] The standard for "passing (OK)" salt spray corrosion resistance test is: after the sample is tested, there is no corrosion, no discoloration, and no rust on the appearance.
[0317] The standard for "failure (NG)" in the salt spray corrosion test is: after the sample is tested, corrosion, discoloration or rust is found on the surface.
[0318] 6. Hardness test of alloy coating
[0319] When testing the hardness of alloy coatings, the sample to be tested adopts a substrate suitable for actual application.
[0320] The surface material of the "substrate suitable for practical application" may include, but is not limited to: aluminum alloy, stainless steel, copper sheet.
[0321] In the following examples, unless otherwise specified, when testing the hardness of the alloy coating, aluminum alloy and stainless steel are used as the substrate, and the alloy coating is deposited on the aluminum alloy and stainless steel using preset preparation parameters to obtain the test sample for testing the hardness of the alloy coating. This is mainly due to the following considerations: During the nanoindentation test, when the probe penetrates the test sample, a strong pressure is formed. At this time, the substrate is required to have a certain toughness. If a brittle silicon wafer is used, cracking may occur during the test, resulting in inaccurate test results. Alloy materials are more suitable as the substrate to be tested for nanoindentation testing due to their excellent toughness. At the same time, the use of alloy materials as the substrate to measure nanohardness is more universal in the field of nanohardness parameter characterization in the field of coated areas.
[0322] The hardness of each film or coating was tested using a nanoindenter model NHT3 produced by Anton-Paar, Austria. It was equipped with a tetrahedral Berkvich indenter, and the indentation depth was set to 100 nm. The load changed with the indentation depth. Five matrix points were tested for each sample and the average value was taken.
[0323] In the following examples, DI water means deionized water.
[0324] The stainless steel sheets, aluminum alloy sheets and silicon sheets in the following embodiments and comparative examples are made of the same material.
[0325] In the following examples, the target material was sputtered by RF-assisted DC sputtering.
[0326] In the following examples, the reference to “there is only one broad peak” in the XRD diagram and the SAED-radial intensity profile diagram, unless otherwise specified, means there is only one characteristic peak, and the peak is a broad peak.
[0327] Example 1.
[0328] In this example, the chemical composition of the Cr-Zr-N alloy coating is Cr 81.6 Zr 13.7 N 4.7 .
[0329] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in deionized water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 - 4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.
[0330] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.
[0331] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 5 sccm, set the gas volume to maintain the Ar: N2 gas volume ratio of 6:1, maintain the furnace pressure at 0.6 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 6 W / cm 2 , the power density of the Zr target was set to 1.5 W / cm 2 , depositing a Cr-Zr-N alloy coating, and controlling the film forming time so that the obtained film thickness is 1300nm.
[0332] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.
[0333] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 81.6 Zr 13.7 N 4.7 .
[0334] Chroma test results: The chroma value of the aluminum alloy substrate sample tested is L: 81.31, a: 0.26, b: 2.88, and the chroma value of the stainless steel substrate sample tested is L: 82.30, a: 0.20, b: 2.45, which is silvery white in color.
[0335] In the salt spray corrosion resistance test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, showing excellent protection properties.
[0336] The hardness value of the aluminum alloy substrate sample tested is 13.7 GPa, and the hardness value of the stainless steel substrate sample tested is 14.6 GPa.
[0337] The SEM cross-section of the test sample was characterized. The cross-sectional morphology can be found in Figure 4 , XRD diffraction pattern, TEM-SAED pattern and radial intensity profile can be found at Figure 5 The SEM test results show that the Cr-Zr-N alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that the diffraction angle 2θ(°) in the XRD diffraction pattern has a broad peak in the range of 30°~50°, and the half-height width of the 2θ(°) diffraction angle in the XRD diffraction pattern in the range of 30°~50° is ≥2°, among which there is only one broad peak with a half-height width of 9.11° in the range of 30°~50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is
[0338] Example 2.
[0339] In this example, the chemical composition of the Cr-Zr-N alloy coating is Cr 61.4 Zr 33.2 N 5.4 , the preparation method is as follows:
[0340] In this embodiment, the target material is a chromium-zirconium alloy target. Figure 3 The original Cr target at the position of the middle Cr target 4 was replaced with a CrZr alloy target having an atomic percentage of Cr and Zr of 65%:35%.
[0341] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, keep at room temperature (about 30°C) for 15 minutes.
[0342] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.
[0343] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use a radio frequency assisted DC power supply to energize the CrZr alloy target, introduce Ar and N2 gas, set the N2 gas flow rate to 7 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 6:1, maintain the furnace pressure at 0.7 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the CrZr alloy target to 5 W / cm 2 , depositing a Cr-Zr-N alloy coating, and by controlling the film forming time, the resulting film thickness is made to be 2500nm.
[0344] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.
[0345] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 61.4 Zr 33.2 N 5.4 .
[0346] The chromaticity value of the aluminum alloy substrate sample tested is L: 79.05, a: 0.43, b: 3.54, and the chromaticity value of the stainless steel substrate sample tested is L: 81.74, a: 0.33, b: 3.04, which is silvery white in color.
[0347] In the salt spray corrosion resistance test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, showing excellent protection properties.
[0348] The hardness value of the aluminum alloy substrate sample tested is 15.1 GPa, and the hardness value of the stainless steel substrate sample tested is 16.3 GPa.
[0349] The SEM cross-section test was performed on the test sample. The cross-sectional morphology can be found in Figure 6 , XRD diffraction pattern, TEM-SAED pattern and radial intensity profile can be found at Figure 7 . The SEM test results show that the Cr-Zr-N alloy coating has a dense structure and no through-column cracks are observed. The XRD test results show that the half-width of the 2θ(°) diffraction angle in the XRD diffraction pattern within the range of 30° to 50° all meets ≥2°, and there is only one broad peak with a half-width of 8.85° in the range of 30° to 50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is
[0350] Example 3.
[0351] In this example, the chemical composition of the Cr-Zr-N alloy coating is Cr 47.1 Zr 17.4 N 35.5 , the preparation method is as follows:
[0352] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.
[0353] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.
[0354] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 42 sccm, set the gas volume to maintain the Ar: N2 gas volume ratio of 2:1, maintain the furnace pressure at 0.8 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 3.9 W / cm 2 , the power density of the Zr target was set to 1.9 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 1600nm.
[0355] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.
[0356] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 47.1 Zr 17.4 N 35.5 .
[0357] The chromaticity value of the aluminum alloy substrate sample tested is L: 73.92, a: 0.43, b: 4.78, and the chromaticity value of the stainless steel substrate sample tested is L: 75.50, a: 0.36, b: 4.69, showing bright silver-white color.
[0358] In the salt spray corrosion resistance test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, showing excellent protection properties.
[0359] The hardness value of the aluminum alloy substrate sample tested is 18.2 GPa, and the hardness value of the stainless steel substrate sample tested is 20.4 GPa.
[0360] The SEM cross-section test was performed on the test sample, and the cross-sectional morphology was as follows: Figure 8 , XRD diffraction pattern as Fig. 9 The SEM test results show that the Cr-Zr-N alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that the diffraction angle 2θ(°) in the XRD diffraction pattern has a broad peak in the range of 30°~50°, and the half-height width of all 2θ(°) peaks in the range of 30°~50° is ≥2°, among which there is only one broad peak with a half-height width of 4.42° in the range of 30°~50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is
[0361] Example 4.
[0362] In this example, the chemical composition of the Cr-Zr-N alloy coating is Cr 52.0 Zr 12.1 N 35.9 , the preparation method is as follows:
[0363] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heated to 150°C, kept at constant temperature for 15 minutes;
[0364] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.
[0365] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 42 sccm, set the gas volume to maintain the Ar: N2 gas volume ratio of 2:1, maintain the furnace pressure at 0.8 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 4.1 W / cm 2 , the power density of the Zr target was set to 1.5 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 1700nm.
[0366] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.
[0367] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 52.0 Zr 12.1 N 35.9 .
[0368] The chromaticity value of the aluminum alloy substrate sample tested is L: 74.16, a: 0.47, b: 4.00, and the chromaticity value of the stainless steel substrate sample tested is L: 75.70, a: 0.41, b: 3.95, which is silvery white in color.
[0369] In the salt spray corrosion resistance test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, showing excellent protection properties.
[0370] The hardness value of the aluminum alloy substrate sample tested is 16.7 GPa, and the hardness value of the stainless steel substrate sample tested is 19.2 GPa.
[0371] The SEM cross-section test was performed on the test sample, and the cross-sectional morphology was as follows: Fig.10 , XRD diffraction pattern as Fig.11 The SEM test results show that the Cr-Zr-N alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that the diffraction angle 2θ(°) in the XRD diffraction pattern has a broad peak in the range of 30°~50°, and the half-height width of all 2θ(°) peaks in the range of 30°~50° is ≥2°, among which there is only one broad peak with a half-height width of 4.04° in the range of 30°~50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is
[0372] Example 5.
[0373] In this example, the chemical composition of the Cr-Zr-N alloy coating is Cr 60.9 Zr 26.1 N 13.0 , the preparation method is as follows:
[0374] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.
[0375] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.
[0376] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 14 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 3:1, maintain the furnace pressure at 0.7 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 5 W / cm 2 , the power density of the Zr target was set to 2.7 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 1000nm.
[0377] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.
[0378] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 60.9 Zr 26.1 N 13.0 .
[0379] The chromaticity value of the aluminum alloy substrate sample tested is L: 79.21, a: 0.41, b: 3.91, and the chromaticity value of the stainless steel substrate sample tested is L: 79.95, a: 0.33, b: 3.73, showing bright silver-white color.
[0380] In the salt spray corrosion resistance test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, showing excellent protection properties.
[0381] The hardness value of the aluminum alloy substrate sample tested is 11.8 GPa, and the hardness value of the stainless substrate sample tested is 13.7 GPa.
[0382] The SEM cross-section test was performed on the test sample. The cross-sectional morphology can be found in Fig.12 , XRD diffraction pattern, TEM-SAED pattern and radial intensity profile can be found at Fig.13The SEM test results show that the Cr-Zr-N alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that the diffraction angle 2θ(°) in the XRD diffraction pattern has a broad peak in the range of 30° to 50°, and the half-height width of all 2θ(°) peaks in the range of 30° to 50° in the XRD diffraction pattern is ≥2°, among which there is only one broad peak with a half-height width of 9.33° in the range of 30° to 50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is
[0383] Example 6.
[0384] In this example, a double-layer film structure is attached to the substrate surface, including a chemical composition of Cr 60.9 Zr 26.1 N 13 The double-layer film structure is denoted as Cr-Zr-N / TiN. At this time, the substrate surface is attached with a multi-layer film structure, wherein the Cr-Zr-N alloy coating provided by the present application is used as an intermediate layer, located between the substrate and the surface layer. The preparation method is as follows:
[0385] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.
[0386] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.
[0387] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 14 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 3:1, maintain the furnace pressure at 0.7 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 5 W / cm 2 , the power density of the Zr target was set to 2.7 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 1000nm.
[0388] Deposition surface layer (second coating): replace the Zr target in the furnace with a Ti target, turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use a DC power supply to energize the Ti target, introduce Ar and N2 gas, set the N2 gas flow rate to 10 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 3:1, maintain the furnace pressure at 0.5 Pa, turn on the bias, set it to -100 V, and set the power density of the Ti target to 5 W / cm 2 , TiN coating is deposited, and by controlling the film formation time, the obtained film thickness is 100nm.
[0389] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.
[0390] After component analysis, the component is Cr 60.9 Zr 26.1 N 13 The alloy coating is provided with a TiN coating on the surface.
[0391] The chromaticity value of the aluminum alloy substrate sample tested is L: 58.85, a: 6.65, b: 12.85, and the chromaticity value of the stainless steel substrate sample tested is L: 59.83, a: 6.82, b: 13.61, showing a golden color. The test results here are the chromaticity values of the surface layer TiN.
[0392] In the salt spray corrosion resistance test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, showing excellent protection properties.
[0393] The hardness value of the aluminum alloy substrate sample tested is 11.7 GPa, and the hardness value of the stainless steel substrate sample tested is 14.2 GPa.
[0394] The SEM cross-section test was performed on the test sample, and the cross-sectional morphology was as follows: Fig.14 The SEM test results show that the Cr-Zr-N alloy coating has a dense structure.
[0395] It should be noted that Fig.14 The vertical cracks in the SEM morphology image correspond to the cracks generated in the process of breaking the silicon wafer, and are not column cracks caused by the growth of Cr-Zr-N film.
[0396] Example 7.
[0397] In this example, a three-layer film structure is attached to the substrate surface, which includes a transition layer (as a bottom coating), an alloy coating containing a Cr-Zr-N alloy material, and a second coating located on the surface. The three-layer film structure is recorded as Cr / Cr-Zr-N / TiN, wherein the transition layer is a Cr layer, and the chemical composition of the Cr-Zr-N alloy coating of the present application is Cr. 60.9 Zr 26.1 N 13 , the chemical composition of the second coating is TiN. The preparation method is as follows:
[0398] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.
[0399] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.
[0400] Deposition of bottom coating (transition layer): Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target, introduce Ar, set the Ar gas volume to 42 sccm, maintain the furnace pressure at 0.5 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 5 W / cm 2 , depositing Cr coating, and by controlling the film forming time, the obtained film thickness is 300nm.
[0401] Deposition of the Cr-Zr-N alloy coating of the present application: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use a radio frequency assisted DC power supply to energize the Cr target and the Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 14 sccm, set the gas volume to maintain the Ar: N2 gas volume ratio of 3:1, maintain the furnace pressure at 0.7 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 5 W / cm 2 , the power density of the Zr target was set to 2.7 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 1000nm.
[0402] Deposition surface layer (second coating): replace the Zr target in the furnace with a Ti target, turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use a DC power supply to energize the Ti target, introduce Ar and N2 gas, set the N2 gas flow rate to 10 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 3:1, maintain the furnace pressure at 0.5 Pa, turn on the bias, set it to -100 V, and set the power density of the Ti target to 5 W / cm 2 , depositing TiN coating, by controlling the film forming time, the obtained film thickness is 100nm;
[0403] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.
[0404] According to the composition analysis, there are three layers of film structure on the surface of the substrate, and the chemical composition is Cr (transition layer), Cr 60.9 Zr 26.1 N 13 (Cr-Zr-N alloy coating of the present application) and TiN (second coating), the three-layer thin film structure is Cr / Cr-Zr-N / TiN.
[0405] The chromaticity value of the aluminum alloy substrate sample tested is L: 56.64, a: 7.07, b: 14.11, and the chromaticity value of the stainless steel substrate sample tested is L: 58.73, a: 7.35, b: 14.35, showing a golden color. The test results here are the chromaticity values of the surface layer TiN.
[0406] In the salt spray corrosion resistance test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, showing excellent protection properties.
[0407] The hardness value of the aluminum alloy substrate sample tested is 13.2 GPa, and the hardness value of the stainless steel substrate sample tested is 15.1 GPa.
[0408] The SEM cross-section test was performed on the test sample. The cross-sectional morphology can be found in Fig.15 The SEM test results show that the alloy coating has a dense structure.
[0409] It should be noted that Fig.15 The vertical cracks in the SEM morphology image correspond to the cracks generated in the process of breaking the silicon wafer, and are not column cracks caused by the growth of Cr-Zr-N film.
[0410] Example 8.
[0411] In this example, the chemical composition of the Cr-Zr-N alloy coating is Cr60.9 Zr 26.1 N 13 , the preparation method is as follows:
[0412] Substrate pretreatment: The copper and silicon wafer samples with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven, and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.
[0413] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.
[0414] Deposition of Cr-Zr-N alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 14 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 3:1, maintain the furnace pressure at 0.7 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 5 W / cm 2 , the power density of the Zr target was set to 2.7 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 1000nm.
[0415] The samples using copper sheets as the substrate were subjected to salt spray corrosion resistance test, hardness test and chromaticity value test, and the samples using silicon sheets as the substrate were subjected to SEM and composition analysis, XRD analysis and TEM test.
[0416] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 60.9 Zr 26.1 N 13 .
[0417] The chromaticity values of the copper substrate sample tested were L: 80.15, a: 0.53, b: 4.63, showing a bright silver-white color.
[0418] In the salt spray corrosion resistance test, the copper substrate sample can pass the 12h test and has certain protective properties.
[0419] The hardness value of the copper substrate sample tested was 7.9 GPa.
[0420] The SEM test results show that the Cr-Zr-N alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that there is a broad peak in the XRD diffraction pattern, and the half-height width of the 2θ(°) diffraction angle in the range of 30° to 50° is ≥2°, among which there is only one broad peak with a half-height width of 9.33° in the range of 30° to 50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is
[0421] Example 9. Cr-Zr-N alloy coating thickness is about 50nm
[0422] The same method as in Example 5 was used, and the chemical composition of the Cr-Zr-N alloy coating was Cr 60.9 Zr 26.1 N 13.0 , the only difference is that the thickness of the Cr-Zr-N alloy coating is adjusted to 50nm.
[0423] The chromaticity value of the aluminum alloy substrate sample tested is L: 80.11, a: 0.41, b: 3.61, and the chromaticity value of the stainless steel substrate sample tested is L: 80.95, a: 0.34, b: 3.43, showing bright silver-white color.
[0424] In the salt spray corrosion resistance test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, showing excellent protection properties.
[0425] The hardness value of the aluminum alloy substrate sample tested was 8.2 GPa, and the hardness value of the stainless steel substrate sample tested was 9.7 GPa.
[0426] Example 10. Cr-Zr-N alloy coating thickness is about 6 μm
[0427] The same method as in Example 5 was used, and the chemical composition of the Cr-Zr-N alloy coating was Cr 60.9 Zr 26.1 N 13.0 The only difference is that the thickness of the Cr-Zr-N alloy coating is adjusted to 6000nm.
[0428] The chromaticity value of the aluminum alloy substrate sample tested is L: 77.31, a: 0.45, b: 3.81, and the chromaticity value of the stainless steel substrate sample tested is L: 76.94, a: 0.34, b: 3.83, showing bright silver-white color.
[0429] In the salt spray corrosion resistance test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, showing excellent protection properties.
[0430] The hardness value of the aluminum alloy substrate sample tested is 22.8 GPa, and the hardness value of the stainless steel substrate sample tested is 24.7 GPa.
[0431] Example 11. Containing doping elements
[0432] In this embodiment, the chemical composition of the Cr-Zr-N alloy coating containing doping elements is Cr 47.1 Zr 17.4 N 30.5 C5, at this time, the sum of the atomic ratios of Cr, Zr, and N is normalized to 100, and the atomic ratio of Cr, Zr, and N is about 49.579:18.316:32.105, and the atomic percentage of the doping element C in the Cr-Zr-N alloy coating is 5%. The preparation method is as follows:
[0433] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.
[0434] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.
[0435] Deposition of the Cr-Zr-N alloy coating of the present application: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use a radio frequency assisted DC power supply to energize the Cr target and the Zr target, introduce Ar, C2H2 and N2 gases, set the N2 gas flow rate to 35 sccm, the C2H2 gas flow rate to 6 sccm, set the gas volume to maintain the Ar: (C2H2 + N2) gas volume ratio of 2:1, maintain the furnace pressure at 0.8 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 3.9 W / cm 2 , the power density of the Zr target was set to 1.9 W / cm 2 , depositing the Cr-Zr-N alloy coating of the present application (specifically a carbon-doped Cr-Zr-N alloy coating), and by controlling the film forming time, the obtained film thickness is 1600nm.
[0436] Stainless steel sheets and aluminum alloy sheets were used as the substrate samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the substrate samples for SEM and composition analysis, XRD analysis and TEM test.
[0437] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 47.1 Zr 17.4 N 30.5 C5.
[0438] The chromaticity values of the aluminum alloy substrate sample tested are L: 72.72, a: 0.41, b: 4.58, and the chromaticity values of the stainless steel substrate sample tested are L: 73.81, a: 0.38, b: 4.27, showing a bright silver-white color. The diffraction angle 2θ (°) in the XRD diffraction pattern has at least one broad peak in the range of 30° to 50°, and the radial intensity profile of the TEM selected area electron diffraction pattern is There is at least one broad peak in the range.
[0439] In the salt spray corrosion resistance test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, showing excellent protection properties.
[0440] The hardness value of the aluminum alloy substrate sample tested is 18.9 GPa, and the hardness value of the stainless steel substrate sample tested is 20.4 GPa.
[0441] According to the experimental exploration results of the inventors, when other non-metallic doping elements (such as Si, B, O, etc.) or metal doping elements (such as Al) are used, high brightness and excellent corrosion resistance can also be provided when the atomic ratio of the doping elements is appropriate (such as 4at%, 2at%). In some embodiments, in the salt spray corrosion resistance test experiment, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test. It can also have at least one broad peak in the XRD diffraction pattern within the range of 30° to 50° diffraction angle 2θ (°), and the radial intensity profile of the TEM selected area electron diffraction pattern is In addition, it also has a relatively high hardness.
[0442] "at %" means atomic percent.
[0443] Example 12.
[0444] In this embodiment, the chemical composition of the alloy coating is Cr 50 Zr 30 N 20 The element composition does not conform to the following combination formula: 63.19-0.925y≤x≤95.79-y and 31.4+0.9y≤x≤18.5y-171.85.
[0445] In this example, the chemical composition of the alloy coating is Cr 50 Zr 30 N 20 , the preparation method is as follows:
[0446] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.
[0447] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.
[0448] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 18 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 3:1, maintain the furnace pressure at 0.7 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 4.5 W / cm 2 , the power density of the Zr target was set to 3.0 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 1000nm.
[0449] Stainless steel sheets and aluminum alloy sheets were used as the substrate samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the substrate samples for SEM and composition analysis, XRD analysis and TEM test.
[0450] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 50 Zr 30 N 20 .
[0451] The chromaticity value of the aluminum alloy substrate sample tested is L: 77.01, a: 0.92, b: 4.52, and the chromaticity value of the stainless steel substrate sample tested is L: 79.06, a: 0.54, b: 3.98, showing a silvery white color. In the salt spray corrosion resistance test, the aluminum alloy substrate sample can pass the 24h test (failed the 48h test), and the stainless steel substrate sample can pass the 96h test (failed the 144h test), with excellent protection characteristics. The hardness value of the aluminum alloy substrate sample tested is 11.6GPa, and the hardness value of the stainless steel substrate sample tested is 12.7GPa.
[0452] The diffraction angle 2θ(°) in the XRD diffraction pattern has at least one broad peak in the range of 30° to 50°, and the radial intensity profile of the TEM selected area electron diffraction pattern is There is at least one broad peak in the range.
[0453] Example 13.
[0454] In this embodiment, the chemical composition of the alloy coating is Cr 49.5 Zr 18.0 N 32.5 The preparation method is as follows:
[0455] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.
[0456] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.
[0457] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 42 sccm, set the gas volume to maintain the Ar: N2 gas volume ratio of 2:1, maintain the furnace pressure at 0.8 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 4.7 W / cm 2 , the power density of the Zr target was set to 1.8 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 1600nm.
[0458] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test, and silicon wafers were used as the matrix samples for XRD analysis and TEM test.
[0459] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 49.5 Zr 18.0 N 32.5 .
[0460] The chromaticity value of the aluminum alloy substrate sample tested is L: 74.52, a: 0.41, b: 4.48, and the chromaticity value of the stainless steel substrate sample tested is L: 75.70, a: 0.32, b: 4.39, showing bright silver-white color.
[0461] In the salt spray corrosion resistance test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, showing excellent protection properties.
[0462] The hardness value of the aluminum alloy substrate sample tested is 18.5 GPa, and the hardness value of the stainless steel substrate sample tested is 19.4 GPa.
[0463] XRD test results (see Fig.16 (A) in the figure shows that the diffraction angle 2θ(°) in the XRD diffraction pattern has a broad peak in the range of 30° to 50°, and the half-height width of all 2θ(°) peaks in the range of 30° to 50° in the XRD diffraction pattern is ≥2°, among which there is only one broad peak with a half-height width of 2.19° in the range of 30° to 50°; the TEM-SAED test results can be found in Fig.16 (B) and (C) in the figure, the radial intensity profile (C) corresponding to the TEM selected area electron diffraction pattern (B) is There is only one broad peak in the range, and the half-height width is
[0464] Regarding the internal mechanism analysis of the high hardness and excellent corrosion resistance of the Cr-Zr-N alloy coating provided by the present application, the inventors of the present application have found through a large number of experimental explorations that for the Cr-Zr-N alloy coating of the present application, when the following two conditions are met at the same time: (1) the diffraction angle 2θ (°) in the XRD diffraction pattern has at least one broad peak in the range of 30° to 50°, and (2) the radial intensity profile of the TEM selected area electron diffraction pattern is The prepared Cr-Zr-N alloy coating has excellent corrosion resistance and high hardness. If only the XRD diffraction pattern has at least one broad peak in the range of 30° to 50° in the diffraction angle 2θ (°) and the radial intensity profile of the TEM-SAED pattern has at least one broad peak in the range of 30° to 50° in the XRD diffraction pattern, the prepared Cr-Zr-N alloy coating has excellent corrosion resistance and high hardness. If there is no broad peak in the range, the prepared Cr-Zr-N alloy coating may have poor corrosion resistance. For example, the corresponding aluminum alloy substrate sample may not pass the 24h salt spray corrosion test. The XRD diffraction pattern has at least one broad peak in the range of 30° to 50°, while the diffraction angle 2θ (°) in the XRD diffraction pattern has no broad peak in the range of 30° to 50°, which may also lead to poor corrosion resistance of the Cr-Zr-N alloy coating. Please refer to the following Comparative Example 4.
[0465] Comparative Example 1.
[0466] In this comparative example, the chemical composition of the alloy coating is Cr 88.9 Zr 11.1 , the preparation method is as follows:
[0467] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.
[0468] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.
[0469] Deposition of Cr-Zr alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar gas, maintain the furnace pressure at 0.6 Pa, turn on the bias voltage and set it to -100 V, and set the power density of the Cr target to 6.7 W / cm 2 , the power density of the Zr target was set to 0.8 W / cm 2 , a Cr-Zr alloy coating was deposited, and by controlling the film forming time, the obtained film thickness was 1900nm.
[0470] Stainless steel sheets and aluminum alloy sheets were used as substrate samples for salt spray corrosion resistance tests, hardness tests and chromaticity value tests. Silicon wafers were used as substrate samples for SEM and composition analysis tests.
[0471] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 88.9 Zr 11.1 .
[0472] The chromaticity value of the aluminum alloy substrate sample tested is L: 83.21, a: -0.21, b: 0.88, and the chromaticity value of the stainless steel substrate sample tested is L: 85.05, a: -0.25, b: 0.79, which is silvery white in color.
[0473] The SEM cross-section test was performed on the test sample. The cross-sectional morphology can be found in Fig.17 The SEM test results show that the alloy coating film has crystal defects, a loose structure, and obvious gaps.
[0474] In the salt spray corrosion resistance test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <24h), and the stainless steel substrate sample failed the 144h test (NG, protection time <48h), and the protection characteristics were poor.
[0475] The hardness value of the aluminum alloy substrate sample tested is 18.5 GPa, and the hardness value of the stainless steel substrate sample tested is 19.6 GPa.
[0476] Comparative Example 2.
[0477] In this comparative example, the chemical composition of the alloy coating is Cr 37.8 Zr 16.2 N 46 , the preparation method is as follows:
[0478] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.
[0479] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.
[0480] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 52 sccm, set the gas volume to maintain the Ar: N2 gas volume ratio of 2:1, maintain the furnace pressure at 0.9 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 3.5 W / cm 2 , the power density of the Zr target was set to 1.8 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 1000nm.
[0481] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.
[0482] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 37.8 Zr 16.2 N 46 .
[0483] The chromaticity value of the aluminum alloy substrate sample tested is L: 61.87, a: 0.57, b: 4.45, and the chromaticity value of the stainless steel substrate sample tested is L: 67.38, a: 0.49, b: 4.29. The color is dull and does not have a metallic color.
[0484] The SEM cross-section test was performed on the test sample. The cross-sectional morphology can be found in Fig.18The test results of XRD diffraction pattern, TEM selected area electron diffraction pattern and radial intensity profile can be found at Fig.19 . The SEM test results show that the alloy coating film has a loose structure and obvious through-column cracks. The XRD test results show that the diffraction angle 2θ (°) in the XRD diffraction pattern has two peaks in the range of 30° to 50°, and both are sharp peaks (2θ peaks with a half-height width value of <2°). Among them, the half-height widths of the two peaks in the range of 30° to 50° are 0.66° and 1.24° respectively. The radial intensity profile of the TEM selected area electron diffraction pattern is There are 2 peaks in the range, with half-height widths of That is, there are two peaks.
[0485] In the salt spray corrosion resistance test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <24h), and the stainless steel substrate sample failed the 144h test (NG, protection time <48h), and the protection properties were poor.
[0486] The hardness value of the aluminum alloy substrate sample tested is 16.6 GPa, and the hardness value of the stainless steel substrate sample tested is 18.1 GPa.
[0487] Comparative Example 3.
[0488] In this comparative example, the thin film structure is TiN, and the chemical composition of the alloy coating is TiN.
[0489] To prepare the coating of this comparative example, the Zr target in the furnace body was replaced with a Ti target, and the preparation method was as follows:
[0490] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.
[0491] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.
[0492] Deposition of TiN coating on the surface: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use a DC power supply to energize the Ti target, introduce Ar and N2 gas, set the N2 gas flow rate to 10 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 3:1, maintain the furnace pressure at 0.5 Pa, turn on the bias, set it to -100 V, and set the power density of the Ti target to 5 W / cm 2, TiN coating is deposited, and by controlling the film formation time, the obtained film thickness is 200nm.
[0493] Stainless steel sheets and aluminum alloy sheets were used as substrate samples for salt spray corrosion resistance tests, hardness tests and chromaticity tests.
[0494] The composition analysis showed that the alloy coating on the substrate surface was composed of TiN.
[0495] The chromaticity value of the aluminum alloy substrate sample tested is L: 57.95, a: 6.45, b: 13.95, and the chromaticity value of the stainless steel substrate sample tested is L: 59.33, a: 6.92, b: 13.91, which is golden in color.
[0496] In the salt spray corrosion resistance test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h).
[0497] The hardness value of the aluminum alloy substrate sample tested is 3.8 GPa, and the hardness value of the stainless steel substrate sample tested is 4.3 GPa.
[0498] Comparative Example 4.
[0499] In this comparative example, the chemical composition of the alloy coating is Cr 39.6 Zr 19.4 N 41 , the preparation method is as follows:
[0500] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.
[0501] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.
[0502] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 45 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 2:1, maintain the furnace pressure at 0.8 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 4.6 W / cm 2 , the power density of the Zr target was set to 2.2 W / cm2 , depositing a Cr-Zr-N alloy coating. By controlling the film forming time, the thickness of the obtained alloy coating film is 1400nm.
[0503] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.
[0504] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 39.6 Zr 19.4 N 41 .
[0505] The chromaticity value of the aluminum alloy substrate sample tested is L: 64.71, a: 0.58, b: 4.15, and the chromaticity value of the stainless steel substrate sample tested is L: 66.38, a: 0.49, b: 4.27, which is silvery white in color.
[0506] The SEM test results show that the alloy coating film has crystal defects, the structure is not dense, and there are obvious through-column gaps. The test results of XRD diffraction pattern, TEM selected area electron diffraction pattern and radial intensity profile can be found in Fig. 20 The XRD test results show that there are two peaks in the diffraction angle 2θ (°) range of 30° to 50° in the XRD diffraction pattern, and both are sharp peaks (2θ peaks with half-height width values < 2°). Among them, the half-height widths of the two peaks in the range of 30° to 50° are 1.87° and 1.02° respectively. The radial intensity profile of the TEM selected area electron diffraction pattern is There are 2 peaks in the range, with half-height widths of That is, there is one peak.
[0507] In the salt spray corrosion resistance test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate.
[0508] The hardness value of the aluminum alloy substrate sample tested is 15.4 GPa, and the hardness value of the stainless steel substrate sample tested is 17.2 GPa.
[0509] Comparative Example 5. Alloy coating thickness 50nm
[0510] The same method as in Comparative Example 4 was used, and the chemical composition of the alloy coating was Cr 39.6 Zr 19.4 N 41 The difference is that the thickness of the alloy coating is different, changing from 1400nm to 50nm.
[0511] In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate. The hardness value of the aluminum alloy substrate sample was 9.1GPa, and the hardness value of the stainless steel substrate sample was 9.8GPa.
[0512] Comparative Example 6. Alloy coating thickness 1000nm
[0513] The same method as in Comparative Example 4 was used, and the chemical composition of the alloy coating was Cr 39.6 Zr 19.4 N 41 The difference is that the thickness of the alloy coating is different, changing from 1400nm to 1000nm.
[0514] In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate. The hardness value of the aluminum alloy substrate sample was 16.5GPa, and the hardness value of the stainless steel substrate sample was 17.9GPa.
[0515] Comparative Example 7: Alloy coating thickness 2500nm
[0516] The same method as in Comparative Example 4 was used, and the chemical composition of the alloy coating was Cr 39.6 Zr 19.4 N 41 The difference is that the thickness of the alloy coating is different, changing from 1400nm to 2500nm.
[0517] In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate. The hardness value of the aluminum alloy substrate sample was 20.5GPa, and the hardness value of the stainless steel substrate sample was 21.1GPa.
[0518] Comparative Example 8: Alloy coating thickness 6000nm
[0519] The same method as in Comparative Example 4 was used, and the chemical composition of the alloy coating was Cr 39.6 Zr 19.4 N 41 The difference is that the thickness of the alloy coating is different, changing from 1400nm to 6000nm.
[0520] In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate. The hardness value of the aluminum alloy substrate sample was 22.1GPa, and the hardness value of the stainless steel substrate sample was 23.7GPa.
[0521] Comparative Examples 9-11. No protective coating
[0522] Aluminum alloy bare chips, stainless steel bare chips and copper bare chips were respectively subjected to salt spray corrosion resistance tests. The results showed that obvious corrosion occurred within 12 hours.
[0523] Result analysis:
[0524] The Cr, Zr and N elements in the Cr-Zr-N alloy coating provided by the present invention satisfy a certain atomic ratio and have a high Cr content.
[0525] The protective coating in Examples 1-5 and 8-13 is a single-layer thin film structure. The Cr-Zr-N alloy coating provided by the present invention directly provides surface protection for the substrate. At this time, the surface of the alloy film product has a higher brightness value; and according to the salt spray corrosion resistance test results, the Cr-Zr-N alloy coating provided in Examples 1-13 can be used as the protective coating itself or as a part of the protective coating, and can provide the substrate with excellent corrosion protection capabilities.
[0526] According to the salt spray corrosion resistance test results, the Cr-Zr-N alloy coatings (Examples 1-13) provided by the present invention can provide excellent corrosion resistance and protection capabilities for the substrate. Example 6 is a double-layer film structure, and the Cr-Zr-N alloy coating provided by the present invention serves as a lower protective layer. A surface layer (TiN) is also attached to the surface of the Cr-Zr-N alloy coating away from the substrate, and the TiN coating serves as a surface protective coating (located on the upper layer); the Cr-Zr-N alloy coating of Example 7 is a three-layer film structure, which includes a transition layer (as a bottom coating), a Cr-Zr-N alloy coating, and a TiN coating located on the surface in sequence from the substrate surface; the Cr-Zr-N alloy coating in Example 11 contains a certain atomic percentage of doping elements (≤5at%).
[0527] Examples 1-7, 9-11, and 13 all use aluminum alloy substrates and stainless steel substrates. The aluminum alloy surface can pass the 48h salt spray corrosion test, and the stainless steel surface can pass the 144h salt spray corrosion test. Example 8 uses a copper substrate, and the copper substrate (copper is a more active alloy) can pass the 12h salt spray corrosion test.
[0528] The elemental composition of the Cr-Zr-N alloy coating in Example 12 does not conform to the following combination formula: 63.19-0.925y≤x≤95.79-y and 31.4+0.9y≤x≤18.5y-171.85, and can pass the 24h salt spray corrosion resistance test on the aluminum alloy surface (but fails the 48h test), and can pass the 96h salt spray corrosion resistance test on the stainless steel surface (but fails the 144h test).
[0529] The alloy coating provided by the present invention can be independently used as a single-layer film, or it can be located in a multi-layer composite film, for example, it can be used as one layer, that is, it can be used as a surface layer (exposed), it can also be used as a bottom coating (contacting the substrate), or it can be used as an intermediate layer (located between the bottom coating and the surface layer).
[0530] According to the results of XRD test and TEM selected area electron diffraction test, the Cr-Zr-N alloy coating (Examples 1-13) provided by the present invention has at least one broad peak (furthermore, all are broad peaks, and the half-height width is ≥2°) in the diffraction angle 2θ (°) in the XRD diffraction pattern within the range of 30° to 50°, and the radial intensity profile of the TEM selected area electron diffraction pattern is ≥2°. There is at least one broad peak in the range (further, all are broad peaks, and the half-height width is ); The Cr-Zr-N alloy coatings of the present application all have a "highly disordered and fully densely packed" atomic arrangement, which is consistent with the highly dense structure in the SEM morphology characterization results.
[0531] In addition, the Cr-Zr-N alloy coatings (Examples 1-13) provided by the present invention also have relatively high hardness, and have both excellent corrosion resistance and high hardness characteristics.
[0532] The bare substrate chips of Comparative Examples 9-11, without a protective coating, were not resistant to salt spray corrosion and suffered obvious corrosion within 12 hours.
[0533] The alloy coating film of Comparative Example 1 lacks N element, the alloy coating films of Comparative Example 2 and Comparative Example 4 have a high content of N element, and Comparative Example 3 does not have a Cr-Zr-N alloy coating (Comparative Example 3 is a TiN coating). It is found that Comparative Examples 1-4 all failed the corrosion test (NG). The inventor speculates that the reason may be: the film structure is not dense, there are gaps, such as penetrating column gaps, which cause the corrosive solution to quickly pass through the gaps and contact the substrate, thereby causing the corrosion resistance of the coating to fail.
[0534] For the alloy coatings of different thicknesses in Comparative Examples 5-8, their hardness and corrosion resistance are significantly inferior to those of the Cr-Zr-N alloy coatings of the present invention of the same thickness. Among them, even if Comparative Example 8 adopts a thickness of up to 6000nm (6 microns), the corrosion resistance is still poor. The speculated reasons may be: the film structure is not dense, and there are gaps, such as the presence of penetrating column gaps, which causes the corrosive solution to quickly pass through the gaps and contact the substrate, thereby causing the corrosion resistance of the coating to fail; although increasing the thickness of the coating can increase the hardness of the coating, the structural defects still exist. The Cr-Zr-N alloy coating provided by the present invention can have excellent corrosion resistance and high hardness characteristics at a relatively low thickness, thereby saving raw materials, simplifying the process, shortening the production cycle, and significantly reducing costs. When the thickness of the alloy coating is relatively thin, the formed alloy film product can present a silvery white metallic color, which is close to the metal color of the substrate, and is more conducive to achieving a beautiful decorative effect without changing the color of the substrate.
[0535] The technical features of the above-mentioned embodiments and examples can be combined in any appropriate manner. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments and examples are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0536] The above embodiments only express several implementation methods of the present invention, which is convenient for understanding the technical solution of the present invention in detail, but it cannot be understood as limiting the scope of protection of the present invention. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present invention, several variations and improvements can be made, which all belong to the protection scope of the present invention. In addition, it should be understood that after reading the above teaching content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and the equivalent forms obtained also fall within the protection scope of the present invention. It should also be understood that the technical solutions obtained by those skilled in the art on the basis of the technical solution provided by the present invention through logical analysis, reasoning or limited experiments are all within the protection scope of the claims attached to the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the content of the attached claims, and the description and drawings can be used to explain the content of the claims.
Claims
1. A Cr-Zr-N alloy material, characterized in that: The chemical formula of the Cr-Zr-N alloy material is (Cr x Zr y N z )M a , M is a doping element, wherein x, y, z and a are each independently an atomic ratio, 47.1≤x≤81.6, 12.1≤y≤33.2, 4.7≤z≤35.9, and 0≤a / (x+y+z+a)≤0.
05.
2. The Cr-Zr-N alloy material according to claim 1, characterized in that: The sum of x, y, and z is 100.
3. The Cr-Zr-N alloy material according to claim 1, characterized in that: y is greater than z.
4. The Cr-Zr-N alloy material according to any one of claims 1 to 3, characterized in that: 63.19-0.925y≤x≤95.79-y and 31.4+0.9y≤x≤18.5y-171.
85.
5. The Cr-Zr-N alloy material according to any one of claims 1 to 3, characterized in that: The doping element is a non-metallic element, a metallic element or a combination thereof; The non-metallic elements include one or more of O, C, B, Si and Ar; The metal elements include one or more of Ti, V, Nb, Mo, Hf, Ta, W, Ni, Mo, Fe, Ag, Au, Cu and Al.
6. The Cr-Zr-N alloy material according to any one of claims 1 to 3, characterized in that: 0≤a / (x+y+z+a)≤0.
02.
7. A Cr-Zr-N alloy coating, characterized in that: The Cr—Zr—N alloy coating comprises a film layer formed by the Cr—Zr—N alloy material according to any one of claims 1 to 6.
8. The Cr-Zr-N alloy coating according to claim 7, characterized in that: The Cr-Zr-N alloy material or the Cr-Zr-N alloy coating meets the following two characteristics: The X-ray diffraction pattern of the Cr-Zr-N alloy material or the Cr-Zr-N alloy coating has a peak in the diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of at least one 2θ (°) diffraction peak in the range of 30° to 50° satisfies ≥ 2°; In the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy coating, the characteristic atomic spacing is taken as the abscissa and the diffraction intensity is taken as the ordinate. There are diffraction peaks in the range of The half-height width of at least one diffraction peak in the range satisfies ≥ 9. The Cr-Zr-N alloy coating according to claim 8, characterized in that: Meet one or more of the following characteristics: The X-ray diffraction pattern of the Cr-Zr-N alloy coating is obtained by Cu target Kα ray; The selected area electron diffraction pattern of the Cr-Zr-N alloy coating is obtained by using TEM characterization technology, with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm.
10. The Cr-Zr-N alloy coating according to any one of claims 7 to 9, characterized in that: The thickness of the Cr-Zr-N alloy coating is d min ~6μm, where d min Selected from 10 nm to 50 nm; Optionally, d min 10 nm, 20 nm, 25 nm, 30 nm, 40 nm or 50 nm; Optionally, the Cr—Zr—N alloy coating has a thickness of 1 μm to 2.5 μm.
11. An alloy film product, characterized in that: It comprises a substrate and the Cr—Zr—N alloy coating according to any one of claims 7 to 10; wherein the Cr—Zr—N alloy coating is located on at least one side of the substrate.
12. The alloy film product according to claim 11, characterized in that: The surface material of the substrate is one of alloy, elemental metal and inorganic non-metallic material; The material type of the alloy includes one or more of nickel-based, iron-based, tungsten-based, titanium-based, silicon-based, aluminum-based, copper-based, cobalt-based, zirconium-based and zinc-based; The elemental metal is any one of zinc, gold, platinum, zirconium, hafnium, niobium, tantalum, nickel, copper, aluminum, iron, silver and chromium; The inorganic non-metallic material includes one or more of ceramics and glass.
13. The alloy film product according to claim 12, characterized in that: The surface material of the substrate is one of light alloys or one of stainless steel alloys; wherein the light alloy includes one or more of titanium alloy, aluminum alloy and magnesium alloy.
14. The alloy film product according to claim 11, characterized in that: Satisfy one or more of the following characteristics: The Cr-Zr-N alloy coating is in direct contact with the substrate or is provided with a transition layer; The Cr-Zr-N alloy coating is located on the surface of the alloy film product or a surface layer is provided on the side of the Cr-Zr-N alloy coating away from the substrate, and the surface layer is a single-layer structure or a multi-layer structure.
15. The alloy film product according to claim 11, characterized in that: The alloy film product is one of 3C digital products, automotive products, aerospace products, wearable products and sports products.
16. Use of the Cr-Zr-N alloy material according to any one of claims 1 to 6 in preparing a high-brightness surface coating or use of the Cr-Zr-N alloy coating according to any one of claims 7 to 10 as a high-brightness surface coating, wherein: According to the Lab method test, the brightness value L of the high-brightness surface coating is ≥70; and the high-brightness surface coating is also a corrosion-resistant protective coating.
17. A method for preparing a Cr-Zr-N alloy coating, characterized in that: The method comprises the following steps: using vapor deposition technology to deposit the constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of the substrate according to a preset atomic ratio, so as to form the Cr-Zr-N alloy coating as claimed in any one of claims 7 to 10.
18. The preparation method according to claim 17, characterized in that: The preparation method of the Cr-Zr-N alloy coating comprises the following steps: under the condition of introducing a mixed gas comprising argon and a nitrogen-containing gas, using one or more target materials comprising chromium and zirconium, sputtering and depositing the constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of the substrate to form the Cr-Zr-N alloy coating.
19. The preparation method according to claim 18, characterized in that: Satisfy one or more of the following characteristics: The temperature of sputtering deposition is 30℃~330℃; The total gas pressure of the mixed gas containing argon gas and nitrogen-containing gas is 0.3 Pa to 1.2 Pa; The target material includes a chromium target and a zirconium target, and the power density of the chromium target is 3.5 W / cm 2 ~6.7 W / cm 2 , and the power density of the zirconium target is 0.5 W / cm 2 ~3.0 W / cm 2 ; The target material includes an alloy target, and the alloy target includes at least two metal elements in the Cr-Zr-N alloy coating; optionally, the target material includes a chromium-zirconium-based alloy target, and the power density of the chromium-zirconium-based alloy target is 4 W / cm 2 ~6 W / cm 2 ; The bias voltage of the substrate is -150 V to -20 V; The sputtering deposition time is 10 min to 150 min; The nitrogen-containing gas is nitrogen gas, and the gas flow rate of the nitrogen gas is 5 sccm to 52 sccm; The nitrogen-containing gas is nitrogen, and the gas volume ratio of argon and nitrogen in the mixed gas is (2-6):1.
Citation Information
Cited By
Cr-ti-n alloy film, cr-ti-n alloy coating, alloy film product and use
WO2025261349A1
